Chemical constituents of Clerodendrum mandarinorum and their chemotaxonomic significance - Shi-Ya Tian; Feng Li; Huai-Qin Liu; Yu Qiu; Wu-Feng Li; Guang-Yan Liang; Chun-Chun Wang; Xue-Long Yan; Shang-Gao Liao; Qin-Feng Zhu (Biochemical Systematics and Ecology, 2026)

Association of structural characteristics with immunostimulatory activity of pectic polysaccharides prepared from Tartary buckwheat sprouts by enzymatic degradation and partial acid hydrolysis - Lin Zhang; Bo Li; Xuan Gao; Mao-Qing Wang; Ya-Nan Cao; Mao-Ling Tan; Yi-Chen Hu; Liang Zou; Dan Li; Yong Deng; Jing-Wei Huang; Ding-Tao Wu (Food Research International, 2026)

Chondroitin sulfate: an environmentally friendly immune inducer enhanceing plant resistance to potato virus X and tobacco mosaic virus - Cui-Hong Hao; Wei Xu; Tian-Qi Liang; Yun-Mei Li; Yi-Lin Guan; Ru-Xin Li; Dan-Ya Ju; Chun-E Peng; Li-Zeng Peng; Qing-Bin Wang (Physiological and Molecular Plant Pathology, 2026)

Fluorescence and SERS dual-mode sandwich lateral flow test strip utilizing concanavalin A modified trimetallic polydopamine with rhodamine B loaded UiO-66 immunoprobe for visual and sensitive detection of Escherichia coli - Wen-Bo Zhao; Xiao Liang; Zi-Tao Zhong; Liu Yuan; Ji-Tao Li; Qiu-Lan Li; Qin-Qin Han; Ya-Ling Yang (Food Bioscience, 2026)

Fabrication of a fluorescence/colorimetric multi-channel sensor array utilizing riboflavin derived bimetallic-doped Ce-MOF based peroxidase mimic for highly efficient determination of heavy metal ions - Xiao Liang; Qiu-Lan Li; Wen-Bo Zhao; Peng Yang; Ya-Ling Yang; Zi-Tao Zhong (Environmental Research, 2026)

A dual-enzymatic activity/SERS dual-mode sensor array based on BSA-Cu nanoflowers for sensitive detection of various foodborne pathogens - Wen-Bo Zhao; Xiao Liang; Liu Yuan; Ji-Tao Li; Ya-Ling Yang; Zi-Tao Zhong (Analytica Chimica Acta, 2026)

IRF2 exacerbates diabetic neuropathic pain by promoting high glucose-induced M1 polarization through IL-6/STAT3 - Yuewei Liang; Ya Ning; Xiaomei Li; Pengcheng Feng; Yingying Liu; Youqing Huang (Genes & Genomics, 2026)

Particulate matter-bound metals and chlorinated paraffins co-exposure: A population-based study on attention-deficit/hyperactivity disorder in Chinese youth - Ya-Qin Zhang; Qi Yang; Hai-Xin Tu; Haseeb Tufail Moryani; Wan-Ting He; Jing-Wen Huang; Dan-Yao Zhou; Yun-Ting Zhang; Li-Xia Liang; Yang Zhou; Li-Zi Lin; Wen-Wen Bao; et al. (Journal of Hazardous Materials, 2026)

Unraveling the molecular evolution and immune functions of Lr-CD40 in Lethenteron reissneri - Liang Zhao; Zihao Yan; Mingwei Du; Xiaoping Song; Xianhui Li; Ya Pang; Ding Li; Guoxiu Ma; Yuetong Zhao; Feng Sun; Yinglun Han (Fish Physiology and Biochemistry, 2026)

Molecular mimicry enables engineering of NLR immune receptors with multi-recognition - Mengyu Qu; Ya Li; Fujia Yang; Guo-Liang Wang; Songbiao Chen (Molecular Plant, 2026)

3D-printable quinoa protein-β-glucan gels with interpenetrating network structures for dysphagia food - Zhen-Yang Quan; Tingting Ji; Jiahan Liu; Qian Li; Ying Chen; Lunan Guo; Jian-Ya Qian; Liang Zhang (Food Bioscience, 2026)

Hepatic Sirt2-PARP1-HMGB1 axis promotes exercise-mediated amelioration of MASH in mice - Shan Li; Wang-Jing Mu; Zi-Ang Zhao; Wan-Qiu Peng; Jie-Ying Zhu; Ruo-Ying Li; Lin-Jing Yan; Yang Li; Hong-Yang Luo; Min Chen; Meng-Ting Yin; Xin Li; et al. (Science China Life Sciences, 2026)

Microglial tunneling nanotubes: an intercellular transfer facilitating mitochondrial dysfunction and neuroinflammation in experimental cerebral malaria - Yan Shen; Yi Wang; Chao Yang; Jun Wang; Yuxiao Huang; Qinghao Zhu; Ganze Li; Tong Li; Jiayi Sun; Jie Ren; Xiaolin Chen; Shuhan Xing; et al. (Apoptosis, 2026)

Heteronemin suppresses chemoresistant oral squamous cell carcinoma cells through ROS-mediated apoptosis and cuproptosis-associated mitochondrial stress - Chiung-Wei Huang; Fan-Li Lin; Chun-Feng Chang; Hsiao-Hsuan Huang; Wan-Ju Wu; Hui-Min Chang; Mei-Ying Lin; Jue-Liang Hsu; Shih-Ya Hung; Chien Hsing Lee (Apoptosis, 2026)

Probiotic Effects of Marichromatium gracile DH-1 on Growth, Stress Resistance, and Water Quality in Juvenile Seahorses: A Potential Strategy for Sustainable Aquaculture - Kai-Hua Geng; Shuai Liang; Yi Zhang; Ya-Juan Wang; Tian-Yu Lu; Yunfeng Liu; Tian Lan; Ya-Nan Lu; Yu-Ting Cong; Yuan Wang; Li Wang; Lian-Shun Wang; et al. (Probiotics and Antimicrobial Proteins, 2026)

A novel UAV-based fusion of spectral and textural features with canopy stratification for accurate estimation of vertical nitrogen distribution in cotton - Guldana Sarsen; Qiu-xiang Tang; Ya-bin Li; Long-long Bao; Yu-hang Xu; Guang-yun Sun; Jian-wen Wu; Yierxiati Abulaiti; Qing-qing Lv; Fubin Liang; Na Zhang; Ren-song Guo; et al. (Computers and Electronics in Agriculture, 2026)

Potential structure-immunostimulatory activity relationship of Tartary buckwheat sprout pectic polysaccharides: Influences of molecular mass and esterification degree - Bo Li; Lin Zhang; Ding-Tao Wu; Qin Yuan; Shengpeng Wang; Mao-Ling Tan; Mei-Lin Feng; Yi-Chen Hu; Liang Zou; Zi-Peng Wang; Ya-Nan Cao; Jing-Wei Huang (Food Research International, 2026)

The physicochemical and simulated digestive characteristics of yam flours processed by different thermal processing methods - Ya Huang; Mei Deng; Xuchao Jia; Lihong Dong; Fei Huang; Qin Ma; Mingwei Zhang; Shan Liang; Yanxia Chen; Fengjuan Li; Ruifen Zhang (Food Chemistry, 2026)

Structure-guided discovery of neutralizing epitopes enables rational design of a multi-epitope nanoparticle vaccine against SVCV - Yu-Ya Li; Liang Zhao; Xue-Feng Wei; Xiao-Hang Ren; Jun-Yao Xia; Zhao Zhao; Bin Zhu (Fish & Shellfish Immunology, 2026)

From air to adipose: Investigating PM2.5-bound chlorinated paraffins and overweight/obesity in Chinese children and adolescents - Qi Yang; Hai-Xin Tu; Yu He; Ya-Qin Zhang; Muhammad Amjad; Jing-Fu Lai; Jing-Wen Huang; Yun-Ting Zhang; Wan-Ting He; Li-Xia Liang; Wen-Wen Bao; Yang Zhou; et al. (Environmental Research, 2026)

Formal synthesis of (-)-warburganal and synthesis of (+)-isodrimenin - Xian-Hui Zhao; Liang Zhao; Yue-Cheng Wu; Ya-Jing Bian; Hui-Jing Li; Yan-Chao Wu (Natural Product Research, 2026)

Impact of habitat biotic factors on selective food hoarding in Brandt's voles - Shan-shan Sun; Tao Liu; Hai-rui Yang; Zhi-liang Zhang; Ya-nan Li; Ming Ming; Hao-ting Zhang; Hai-wen Yan; Xin Li; Lin-lin Li; Na Zhu; Xiao-dong Wu; et al. (Journal of Arid Environments, 2026)

Boron neutron capture therapy-driven secretory-autophagy sorting of immunogenic cargo into extracellular vesicles converts tumors into precision autologous vaccines - Xin Pan; Linwen Lv; Zhiliang Hu; Jiayi Wang; Haojun Liang; Jiaxin Wan; Junhui Zhang; Ruyu Yan; Juan Li; Ya-nan Chang; Xue Bai; Lu Zhang; et al. (Chemical Engineering Journal, 2026)

Cell-specific gene expression plasticity in response to hypoxia promotes high-altitude adaptive evolution - Wen-Tian Wei; Ze Yan; Hui Wu; Ming-Liang Zhou; Dong-Xin Mo; Xing Wan; Rui Ma; Mei-Ming Wu; Jia-Hui Huang; Ya-Jing Liu; Ji Yang; Meng-Hua Li (Science China Life Sciences, 2026)

A novel salt-tolerant purple photosynthetic bacterium Afifella marina TC201-1 for sustainable treatment of saline aquaculture wastewater - Shuai Liang; Kai-Hua Geng; Ding-xian Xu; Ya-Juan Wang; Wei-Yu Du; Yun-Feng Liu; Ya-Nan Lu; Li Wang; Yuan Wang; Jing Gu; Yu-Ting Cong; Lian-Shun Wang; et al. (Journal of Water Process Engineering, 2026)

Cell type-specific contribution of low-density lipoprotein receptor to atherosclerosis - Wei-Hui Li; Yu-Liang Zhang; Ya-Fen Zhang; Zhenyang Yu; Liang Chen; Hao-Yu Fang; Liang Cheng; Bao-Liang Song; Jie Luo (Science China Life Sciences, 2026)

Histomorphological analysis of the relationship between Helicobacter pylori infection of the gastric mucosa and host immunity strength - Yang-kun Wang; Quan-wei Guo; Hai-ying He; Ying-ying Li; Chao-ya Zhu; Ping Li; Bo Jiang; Su-nan Wang; Si-liang Xu (Journal of Molecular Histology, 2026)

Ursolic acid nanoemulsion system for inhibition of goji berry black mold caused by Alternaria alternata - Liang Liu; Huaiyu Zhang; Junjie Wang; Yueli Zhou; Dayuan Chen; Ya Yang; Jing Li; Haotian Ma; Zhao-Jun Wei (Food Chemistry, 2026)

AID/APOBEC-like cytidine deaminases are important mediators of VLR-based adaptive immunity in lampreys - Zihao Yan; Jingjing Lu; Yuesi Zhou; Liang Zhao; Ding Li; Huining Jia; Ayqeqan Nurmamat; Min Xiu; Shuyuan Zhang; Ruyu Zhuang; Ya Pang; Tiesong Li; et al. (Fish & Shellfish Immunology, 2026)

Effects of adding Afifella marina on growth performance, intestinal health, and microbial community of juvenile Hippocampus abdominalis - Shuai Liang; Kai-Hua Geng; Yi Zhang; Ya-Juan Wang; Tian-Yu Lu; Tian Lan; Ya-Nan Lu; Yuan Wang; Jing Gu; Yu-Ting Cong; Li Wang; Lian-Shun Wang; et al. (Aquaculture International, 2026)

Diffusion dynamics coupled with in situ etching enable controlled growth of InAs quantum dots with narrow SWIR emission - Feng Zhao; Hong-Wei Duan; Ye Wang; Zong-Shuo Liu; Zhou Li; Sanxia Yin; Shulin Chen; Ya-Kun Wang; Liang-Sheng Liao (Science Bulletin, 2026)

Impact of pitaya peel powder particle size on bread quality and functional properties: a sustainable strategy for agro-industrial waste upcycling - Ying Chen; Qi Li; Zhen-Yang Quan; Wen Liu; Lunan Guo; Liang Zhang; Linghan Meng; Xiaojuan Xu; Jian-Ya Qian (Food Chemistry, 2026)

Cloning, tissue distribution, and stimulus-responsive mRNA expression of CD10 (neprilysin) in Lethenteron reissneri - Liang Zhao; Zihao Yan; Xianhui Li; Ya Pang; Ding Li; Guoxiu Ma; Yuetong Zhao; Mingwei Du; Feng Sun; Yinglun Han (Fish & Shellfish Immunology, 2026)

Targeted photodynamic therapy for multispecies dental biofilms using liposome encapsulated p-Toluquinone - Chen Liang; Yongli Li; Zuan-Tao Lin; Zhilong Wang; Ya He; Yan Dong; Zihan Ran; Sophia Zhang; Ying Zhao; Songling Wang; Mei X. Wu (Chemical Engineering Journal, 2026)

A phytoalexin-inspired, natural product-based marine antifouling coating with synergistic active antimicrobial and passive anti-adhesive performances - Liang Ma; Xing-Yu Lei; Qi Xu; Ya-Fu Li; Yu-Hao Li; Peng-Fei Chen; Jian-Cai Chen; Hui-Jing Li; Yan-Chao Wu (Chemical Engineering Journal, 2026)

Experimental Investigation of Porosity and Permeability of Reservoir Rock Under the Action of CO2 and Its Oil Displacement Effect - Bin Zhang; Jun Luo; Fajian Nie; Liang Wang; Xi Jiang; Wei Li; Ya Meng (Natural Resources Research, 2026)

Carbon Mitigation through EIAs in China: Evidence, Mechanisms, and Policy Implications - Peng Kuai; Liang Li; Peng Zhou; Runhe Cheng; Ya Chen; Mudan Wang (Environmental Management, 2026)

Quantitative prediction of fracture distribution in deep conglomerate reservoirs of the Bozhong 19-6 South structure, offshore Bohai Bay Basin, East China: Insights from numerical simulation of multiphase strike-slip regimes - Liang Zhou; Chao Deng; Li-ya Da; Yu Xia; He-wei Hu; Kai Ji; Chang-yu Fan; Yong Cheng; Yu-jie Ning; Xiao-fang Yang (Marine and Petroleum Geology, 2026)

Observation of out-of-plane ferroelectricity in ∼5 nm ultrathin SrBi2Ta2O9 films for memristors and synapses application - Li-Ping Tan; Xue-Feng Hu; A-Long Li; Wei-Wei Qing; Ming Zhou; De-Bao Yu; Guo-Peng Zhang; Qing-Qing Mu; Zi-Long Wang; Xiao-Liang Wang; Ya-Li Bi; Wei Zhang (Chemical Engineering Journal, 2026)

Glycogen Synthase Kinase-3β Inhibition Ameliorates Synaptic and Mitochondrial Dysfunction in a Sporadic Alzheimer’s Disease–Like Model - Ya-Han Wang; Peng-Li Ding; Hao Qin; Kai-Xin Zhang; Jin-Wen Ge; Da-Hua Wu; Le Xie; Kun Liang (Molecular Neurobiology, 2026)

Prediction Of Relative Permeability Curve Based On Machine Learning Driven By Logging Data - Jia-ru Zou; Shou-dong Huo; En-liang Liu; Tong-sheng Zeng; Lian-lian Hu; Ya-ying Song; Meng Li (Applied Geophysics, 2025)

3D printing-driven functional food innovation: construction of personalized nutritional system and precise regulation mechanism of texture structure - Meng-yuan Wang; Meng-yao Zhang; Xiao-hu Luo; Li-guo Liang; Ya-nan Liu (Trends in Food Science & Technology, 2025)

1-NP hijacks endocrine-metabolic checkpoints and disrupts testicular steroidogenesis by suppressing the cAMP-PKA-CREB-HMGCR axis - Xin-xin Zhu; Wei-wei Zhang; Ming-yue Hao; Zheng-ya Chen; Bai-fan Wan; Ming-hui Niu; Xiu-liang Li; Jian-hua Wei; Su-ya Liu; Shuang-ling Mi; Hua Wang; De-xiang Xu; et al. (Toxicology Letters, 2025)

Petrogenesis of Triassic intermediate-felsic intrusions from three skarn tungsten deposits in the East Kunlun Orogenic Belt, NW China: Evidence from zircon U Pb geochronology, petrochemistry, and Hf isotopic characteristics - Yan Tan; Jin-Xiang Li; Fang Xu; Yan-Qian Yang; De-Xin Zhang; Hua-Liang Lai; Sheng-Qiang Ma; Shun-Long Yang; Yi-Jun Yang; Chen Wu; Ya-Hui Yue; Chao Wang; et al. (Lithos, 2025)

The variation of the East Asian summer monsoon on multi-centennial scale during 8.3–2.9 ka BP - Chao-Jun Chen; Ya-Xi Dong; Yao Wu; Jian Zhang; Hai-Bo Wang; Yan-Xia Xue; Wen-Jun Sun; Man-Ping Xie; Hai Cheng; Jun-Yun Li; Ming-Qiang Liang; Ting-Yong Li (Global and Planetary Change, 2025)

Re-O-Ti interfaces boosting heterolytic H2 activation: Mechanochemical synthesis of Re/TiO2 for sustainable fatty alcohol production - Songyin Yu; Zhichao Sun; Ya Wei; Changhai Liang; Chuang Li (Chemical Engineering Journal, 2025)

Identification, Characterization, and Expression Profiling of Oryza Sativa Betaine Aldehyde Dehydrogenase Genes Exposed to Realistic Environmental Contamination of Oxyfluorfen - Yi Zhuo Wang; Jun Jin Lu; Xu Zhen Shi; Ya Nan Qu; Li Qing Zeng; Xiao Liang Liu; Xi Ran Cheng; Yan Hui Wang; Zhao Jie Chen (Tropical Plant Biology, 2025)

Exploring the evolutionary conservation and functional implications of Endothelin Converting Enzyme 1 (ECE1) in lamprey (Lethenteron reissneri) - Shuyuan Zhang; Zihao Yan; Ayqeqan Nurmamat; Ruyu Zhuang; Yuesi Zhou; Min Xiu; Ya Pang; Ding Li; Liang Zhao; Xin Liu; Yinglun Han (Fish Physiology and Biochemistry, 2025)

Resistance to peripheral fatigue of diglyceride-based food for special medical purposes and its acting mechanism - Liang Jiang; Ya Mao; Mingke Li; Xiaona Yang; Xuewu Zhang (Food Bioscience, 2025)

Evolutionary conservation and Immunoregulatory function of LOXL3 gene in lamprey - Ya Pang; Zihao Yan; Yicheng Gao; Ding Li; Liang Zhao; Guoxiu Ma; Yuetong Zhao; Mingwei Du; Feng Sun; Yinglun Han (Fish & Shellfish Immunology, 2025)

Tilted evaporator with “1 + 1 + 1 > 3” synergistic strengthening in photothermal, photocatalytic and antibacterial performance for enhanced treatment of high-salinity dye wastewater - Yuxin Yang; Qian Liang; Naif Abdullah Al-Dhabi; Yanfei Ya; Jun Li; Wangwang Tang; Changkun Liu (Desalination, 2025)

Androgen induces 3′UTR shortening of de novo lipogenesis genes by alternative polyadenylation in prostate cancer cells - Wei-Jie Sun; Fei Liang; Hui Zhao; Yun-Mei Wang; Zhong-Yin Zhou; Hui Xu; Hang Liu; Dong Tang; An-Long Xu; Yong-Gui Fu; Xi Li; Jun Ouyang; et al. (Science China Life Sciences, 2025)
Alternative polyadenylation (APA) is a pervasive mechanism that is emerging as a formidable player in post-transcriptional regulation. The transcriptional landscape can be altered via APA in response to various stimulating factors. Using the PacBio single-molecule long-read sequencing method, we present for the first time the 3′UTR landscape and reveal a global increase of APA events in prostate cancer (PCa) LNCaP cells in response to androgen dihydrotestosterone (DHT), a critical regulator of PCa progression. With evidence from differential gene expression analyses of Illumina RNA-sequencing data, we demonstrated that genes with DHT-induced changes in both expression and APA were enriched in lipid metabolism. These genes predominantly supported de novo fatty acid synthesis, such as FASN and ACSL3 . Furthermore, we showed that an isoform switch to the proximal poly(A) site of these genes depended on the androgen receptor, and the expression of cancer-associated genes was upregulated by the escape of miRNA-regulated repression machinery. To address the role of key gene shortening in PCa, we prepared 22RV1-FS cells missing the distal poly(A) signal of FASN in the AR + PCa cell line 22RV1 using CRISPR/Cas9 technology. As expected, the edited 22RV1-FS cells overexpressed FASN mRNA and protein and were inclined to cell proliferation in vitro and tumorigenesis in vivo . Interestingly, we found that FASN transcripts with a shortened 3′UTR were significantly increased in advanced PCa and castration-resistant prostate cancer compared with benign prostate hyperplasia, suggesting a possible association between usage of the proximal poly(A) site and disease progression. Therefore, our study highlights the importance of the APA mechanism in response to DHT stimulation in PCa cells and provides a novel regulatory mechanism through which DHT-induced APA causes altered expression of de novo lipogenesis genes, with a possible association with the progression of PCa.

Comparative transcriptomics unveils nitric oxide delaying leaf senescence in Chinese flowering cabbage by enhancing BrGATA21-mediated ROS scavenging - Zhen-liang Mou; Ze-xiang Zeng; Zong-li Liu; Wei Wei; Wei Shan; Jian-fei Kuang; Wang-jin Lu; Jian-ye Chen; Ya-ting Zhao (Postharvest Biology and Technology, 2025)

Latest progress based on doped-TiO2 photocatalysis materials: Fabrication and applications - Xiao-Ni Qi; Ya-Qi Zhu; Hui Yuan; Zi-Xuan Xu; Hao-Ran Guo; Zhen-Liang Li (Journal of Water Process Engineering, 2025)

Construction of LncRNA-miRNA-mRNA regulatory network in IgA nephropathy mice model by RNA-sequencing and bioinformatics analysis - Wen Jia Zheng; Tao Liu; Xiao Li Zhu; Yu Ting Zhang; Liang Bing Wei; Ya Chen Gao; Xing Xing Zhuang; Jia Rong Gao (Genes & Genomics, 2025)

Millimeter-scale leaf litter placement modulates carbon dioxide and methane emissions in wetlands - Hao Liu; Yining Zhang; Yu-Jia Cai; Zi-Yan Liu; Liang Li; Ya-Qin Wang; Xiao Shu; Royston Goodacre; Zheng Chen (Applied Geochemistry, 2025)

GSDME-dependent astrocyte pyroptosis promotes the progression of neuroinflammation in experimental cerebral malaria - Jun Wang; Qinghao Zhu; Guodong Tong; Kangjie Yu; Jiao Liang; Yuxiao Huang; Yi Wang; Chao Yang; Tong Li; Weilu Liang; Ganze Li; Xiaoran Liu; et al. (Apoptosis, 2025)

Genomic analysis of Caballeronia sp. DA-9 reveals its role in glutathione metabolism - Jun Li; Kun Liang; Ya Ma; Nan Zhang (Marine Genomics, 2025)

Isoliquiritigenin alleviates radiation-induced intestinal injury in lung cancer by inhibiting TNF-α/caspase3 signaling pathway - Ya-ping Chen; Liang-liang Shi; Yang-yang Li; Yi-Ming Zhang; Shang-zu Zhang; Hong-dou Hou; Yan Chen; Qi-hong Zhuo; Yong-qi Liu; Ben-jun Wei; Li-ying Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Spatiotemporal distribution of neonicotinoids in urban rivers: implications for rainfall-driven pollution in Guangzhou, China - Ya-Ya Cai; Nan Li; Qian-Qian Zhang; Yue-Hong Liu; Jian-Liang Zhao; Guang-Guo Ying (Science of The Total Environment, 2025)

Nicotianamine facilitates zinc translocation from roots to shoots in the nickel hyperaccumulator Odontarrhena chalcidica - Teng-Hao-Bo Deng; Ya-Zhou Wang; Bing-Lan Mo; Ting Liu; Lei Li; Ye-Tao Tang; Dian Wen; Yong-Dong Huang; Sheng-Sheng Sun; Xu Wang; Rui-Ying Du; Jean-Louis Morel; et al. (Plant and Soil, 2025)

Leaf and Root Traits Show Contrasting Resource Exploitation Strategies, but Converge Along Elevation in the Hengduan Mountain Forests - Jie Song; Sebastian Seibold; Liang‐Liang Ma; Jia‐Yun Zou; Jie Liu; Ming‐Shu Zhu; Wei Zheng; Zhi‐Qiong Mo; Sheng‐Ping Ming; Jin Li; Kun Xu; De‐Zhu Li; et al. (Journal of Biogeography, 2025)
Aim The variations of leaf and root traits in communities are associated with above‐ and below‐ground resource exploitation strategies and are used to infer community assembly processes along environmental gradients. However, little is known about variations in leaf and root traits and their drivers along elevations in mountain forests. Location Yulong Mountain, southeastern Hengduan Mountains, Southwest China. Taxon Seed plants. Methods We measured six leaf traits and seven root traits across 47 woody species and collected environmental variables from forest plots along a 1200 m elevational gradient. We employed linear mixed models to examine how resource exploitation strategies (community‐weighted mean, CWM) and functional diversity (standardised effect size of RaoQ, SES.RaoQ) associated with leaf and root traits varied along elevations. Furthermore, we determined the relative effects of environmental variables on these metrics. Results We observed that the resource exploitation strategy of leaves shifted from an acquisitive to a conservative strategy (higher leaf carbon concentration) with increasing elevation. Conversely, root trait variation exhibited an opposite trend, shifting from a conservative to an acquisitive strategy (higher root branching intensity but lower root diameter and root tissue density) along elevations, potentially influenced by mycorrhizal interactions. We detected functional convergence for leaf and root traits across elevations, with a greater degree of functional convergence at high elevations. Leaf trait convergence was closely linked to soil nitrogen conditions, whereas root trait convergence was associated with soil organic carbon levels. Main Conclusions Our results highlight that the patterns of resource exploitation strategies along elevational gradients are decoupled for leaf and root traits, with distinct environmental factors shaping the convergence of root and leaf traits. We argue that forest communities in mountain ecosystems may modify their resource exploitation strategies and functional diversity through varying combinations of leaf and root traits to improve resilience to future global change.

Molecular identification of heterotrophic nitrification and aerobic denitrification bacteria: From methods development to application demonstration - Rui-chun Yang; You-wei Cui; Zhen-ying Li; Ming-teng Li; Liu-xu Jiang; Ya-nan Mi; Yuan Sui; Hui-kai Liang (Water Research, 2025)

Insights into the synergistic effects of exogenous glycine betaine on the multiphase metabolism of oxyfluorfen in Oryza sativa for reducing environmental risks - Zhao Jie Chen; Xu Zhen Shi; Ya Nan Qu; Si Ying Li; Gan Ai; Yi Zhuo Wang; Li Qing Zeng; Xiao Liang Liu; Xuesheng Li; Yan Hui Wang (Journal of Hazardous Materials, 2025)

Effects of mono- and di-glycerides/phospholipids (MDG/PL) on the bioavailability of lutein and DHA in rats: more effective for lutein - Shu-zhen Huang; Huan-huan Yin; Fang Tian; Liang Wang; Wen-jing Wu; Xiang Li; Yanrong Zhao; Xiao-ya Wang; Yun Li; Megan Terp; Ying-yi Mao; Jin-yao Chen (Food Bioscience, 2025)

Rapid and efficient nitrogen removal by a novel heterotrophic nitrification-aerobic denitrification bacteria Marinobacterium maritimum 5-JS in aquaculture wastewater: Performance and potential applications - Fu-Rong Wang; Shi-Yu Feng; Shuai Liang; Wei-Yu Du; Long-Qi Wang; Yu-Wei Zhang; Jia-Yu Ren; Shuang Gao; Yu-Jie Zhu; Yu-Ting Cong; Li Wang; Jing Gu; et al. (Environmental Research, 2025)

Rational design of vitamin B3 derived bimetallic doped Cu-MOF with laccase-like activity for the colorimetric detection of Cr3+ - Xiao Liang; Qiu-Lan Li; Wen-Bo Zhao; De-Zhi Yang; Ya-Ling Yang; Zi-Tao Zhong (Journal of Environmental Chemical Engineering, 2025)

The nickel hyperaccumulator Odontarrhena chalcidica (Brassicaceae) preferentially takes up zinc over nickel - Ya-Zhou Wang; Ke-Rui Geng; Bing-Lan Mo; Ting Liu; Ye-Tao Tang; Dian Wen; Fu-Rong Li; Xu Wang; Lei Li; Rui-Ying Du; Antony van der Ent; Teng-Hao-Bo Deng; et al. (Plant and Soil, 2025)

Helicobacter pylori VacA-induced gastric mucosal atrophy: a comparative analysis with other forms of atrophic gastritis - Yang-Kun Wang; Wen-Rui Chen; Ling-Yan Lu; Ying-Ying Li; Rui-Kun Qiu; Chao-Ya Zhu; Fa-Shun Zhang; Su-Nan Wang; Si-Liang Xu (Journal of Molecular Histology, 2025)

Machine learning-enhanced flavoromics: Identifying key aroma compounds and predicting sensory quality in sauce-flavor baijiu - Shuai Li; Yueran Han; Li Wang; Ya Zhang; Fan Wang; Youming Ou; Haoying Li; Liang Yang; Shuyi Qiu; Jun Lu (Food Chemistry, 2025)

A facile colorimetric sensor based on Fe3O4 magnetic nanoparticles with intrinsic catalytic activity for the rapid and selective detection of ochratoxin A - Xiao Liang; Qiu-Lan Li; Ji-Tao Li; Wen-Bo Zhao; De-Zhi Yang; Ya-Ling Yang; Zi-Tao Zhong (Food Chemistry, 2025)

S-scheme heterojunction of WO3/metal-covalent organic frameworks for artificial photosynthetic CO2 reduction - Liang Fang; Li-Wen Bai; Di Wu; Hong-Tu Che; Yanxia Jiang; Ya Wang; Hong Dong; Feng-Ming Zhang (Chemical Engineering Journal, 2025)

Spatiotemporal comparative analysis of three carbon emission inventories in mainland China - Liang Zheng; Shenshen Li; Xuefei Hu; Fengbin Zheng; Kun Cai; Ning Li; Ya Chen (Atmospheric Pollution Research, 2025)

Identification and characterization of anthocyanins’ composition and regulatory genes involved in anthocyanins biosynthesis in water dropwort (Oenanthe javanica) - Kai Feng; Nan Sun; Ya-Qing Bian; Wu-Di Rui; Ya-Jie Yan; Zhi-Yuan Yang; Jia-Lu Liu; Zi-Qi Zhou; Shu-Ping Zhao; Peng Wu; Liang-Jun Li (Planta, 2025)

The antinociceptive and anti-alpha-glucosidase effects of glucosides from Hemiphragma heterophyllum Wall. - Chun-Fang Wen; Yu-Xiao Li; Ke-Xin Nie; Qiu He; Ya Lu; Zi-Liang Wang; Xi-Shan Bai; Yan-Hong Li; Xiang-Zhong Huang (Natural Product Research, 2025)

Large language models for diabetes training: a prospective study - Haoxuan Li; Zehua Jiang; Zhouyu Guan; Yuqian Bao; Yuexing Liu; Tingting Hu; Jiajia Li; Ruhan Liu; Liang Wu; Di Cheng; Hongwei Ji; Yong Wang; et al. (Science Bulletin, 2025)

Targeted isolation of lignans and triterpenoids from kadsura coccinea by molecular networking and anti-RA-FLS activity - Shi-qi Liu; Qing-ling Xie; Ya-si Deng; Ling Liang; Han-wen Yuan; Bin Li; Huang-he Yu; Xing Tian; Yi-xing Qiu; Guy Paulin Kemayou Mouthe; Nuzhat Shehla; Ye Zhang; et al. (Phytochemistry, 2025)

Insertional mutagenesis of AIDA or CYP720B1 in the green alga Chlamydomonas reinhardtii confers copper(II) tolerance and increased biomass - Ya Li; Lin Jiang; Chuang Xu; Suhui Wang; Yunyao Qian; Yiqiong Wu; Chenyu Miao; Zhouzhou Dong; Liang Wang (Journal of Hazardous Materials, 2025)

Effects of mixed exposure to PFAS on adolescent non-alcoholic fatty liver disease: Integrating evidence from human cohorts, toxicogenomics, and animal models to uncover mechanisms and potential target sites - Xiushuai Du; Dan-Lin Li; Xueming Xu; Yitian Wu; Zhiyuan Du; Gang Liang; Yue-Zu Li; Ya-Jie Zheng; Yu Qin; Kelei Qian; Jing Xu; Liping Gao; et al. (Journal of Hazardous Materials, 2025)

Effect of scenting process on the taste profile of jasmine green tea and the potent bitterness-enhancing compound in jasmine flowers - Jia-Ying Chen; Wen-Wen Luo; Wen-Xuan Li; Ya-Nan Zheng; Xin-Qiang Zheng; Jian-Liang Lu; Yue-Rong Liang; Jian-Hui Ye (Food Research International, 2025)

The modification effect of concentration on the correlation between ambient ozone and psoriasis: a hospital-based time-series study - Hao Liu; Kexue Wang; Lili Yang; Yumeng Zhou; Yuanchao Li; Enjie Tang; Dawei Li; Ya Gan; Chunbei Zhou; Liangmei Wang; Xiaohua Liang; Tongjian Cai (International Journal of Biometeorology, 2025)

Genome-wide identification and expression of Oryza sativa haloacid dehalogenase genes associated with oxadiazon metabolism - Zhao Jie Chen; Ya Nan Qu; Jun Jin Lu; Si Ying Li; Gan Ai; Xu Zhen Shi; Li Qing Zeng; Xiao Liang Liu; Dan Lu (Genetic Resources and Crop Evolution, 2025)

Improvement of the gel properties of curdlan gel by hydrogen bonding interaction with trehalose - Long-Qing Li; Le-Yi Pan; Tong-Xin Liang; Mingyu Jin; Ya-Hui Yu; Xiangying Yu; Xiaozhen Liu; Fengyuan Liu; Yuting Li; Jing-Kun Yan (Food Hydrocolloids, 2025)

Enhanced nano-LC-MS for analyzing dansylated oral cancer tissue metabolome dissolved in solvents with high elution strength - Ya-Ju Hsieh; Cheng-Yu Hung; Yi-Ting Chen; Yu-Tsun Lin; Kai-Ping Chang; Wei-Fan Chiang; Chih-Yen Chien; Chih-Ching Wu; Liang Li; Jau-Song Yu; Kun-Yi Chien (Analytica Chimica Acta, 2025)

Characterizing immune responses of grey mullet (Mugil cephalus) to Nocardia seriolae ex vivo and in vivo - Ya-Ting Wang; Chien-Yueh Lee; Ching-Hung Chan; Liang-Chuan Lai; Mong-Hsun Tsai; Eric Y. Chuang; Li-Han Chen (Aquaculture International, 2025)

High glucose induces renal tubular epithelial cell senescence by inhibiting autophagic flux - Ying Zhang; Yu Zhao; Yu-Qiu Liu; Ya-Ping Fang; Li Sun; Shan-Zhai Wei; Xiao-Dong Zhu; Xiao-Liang Zhang (Human Cell, 2025)

Gestational exposure to carbon black nanoparticles triggered fetal growth restriction in mice: The mediation of inactivating autophagy-lysosomal degradation system in placental ferroptosis - Jing Li; Hongying Gao; Zehua Xu; Biling Gao; Liang Zhang; Bowen Su; Shijing Yang; Jiangling Liu; Ya Liu; Xiuxiu Wang; Heng Wang; Yi Lin; et al. (Science of The Total Environment, 2025)

Inhibiting overgrowth of filamentous fungi by magnetic powders: Combination effects of particle interface toxicity and magnetic microbe - Dong-Xu Zhou; You-Wei Cui; Ya-Nan Mi; Liu-Xu Jiang; Ming-Teng Li; Hui-Kai Liang; Hui-Juan Yan; Xu Wang (Chemical Engineering Journal, 2025)

Mechanism, diffusion, and kinetics characteristics of nitrocellulose denitrification revealed by DFT and MD - Shen Li; Zhong-Xin Liu; Shi-Ying Li; Ya-Jun Ding; Zhong-Liang Xiao; Jie Zhou; Xiao-Qing Wu; Hong-Lei Fan; Zheng-Hong Luo; Xi-Bao Zhang (Chemical Engineering Journal, 2025)

Study on Mechanism of Water and Mud Inrush in Deep-Buried Large-Section Tunnel Crossing Water-Rich Fault Fracture Zone - Zu-liang Zhong; Zhuo Shen; Hong-yan Qiao; Ya-peng Li; Kai-xin Zhu (Rock Mechanics and Rock Engineering, 2025)

Huanglian decoction prevents and treats radiation-induced intestinal injury in lung cancer by regulating endoplasmic reticulum stress - Liang-liang Shi; Ya-ping Chen; Hao-ming Guo; Xue-peng Wang; Yang-yang Li; Shuai-zhe Wang; Shang-zu Zhang; Qi-hong Zhuo; Yong-qi Liu; Ben-jun Wei; Li-ying Zhang (Journal of Natural Medicines, 2025)

Intramolecular distance-regulated G4 DNA enzymatic activity-based chromophotometric system for visual monitoring of diquat - Ya You; Wei-Guo Yang; Shun Zhang; Ming-Li Su; Qi-Lin Peng; Wan-Jiang Zhao; Ruo Yuan; Shang-Cheng Xu; Wen-Bin Liang (Analytica Chimica Acta, 2025)

Temperature differentially regulates estuarine microbial N2O production along a salinity gradient - Tie-Qiang Mao; Yong Zhang; Ya-Fei Ou; Xiao-Fei Li; Yan-Ling Zheng; Xia Liang; Min Liu; Li-Jun Hou; Hong-Po Dong (Water Research, 2024)

Coupling of anthropogenic activities and natural factors on dissolved organic matter: Insights from coastal urban rivers in southern China - Ya Wang; Yafeng Zhang; Shi Tang; Yongjin Liang; Renren Wu; Penghui Li (Journal of Environmental Chemical Engineering, 2024)

Slide-shaped cotton-based photocatalytic solar evaporator with dual mutually strengthening functions for simultaneous desalination and dynamic fast dye removal - Jun Li; Qian Liang; Yuxin Yang; Yanfei Ya; Dahang Deng; Changkun Liu (Desalination, 2024)

A compound heterozygous mutation of ERCC8 is responsible for a family with Cockayne syndrome - Meng-Wei Liu; Cheng-Feng Hu; Jie-Yuan Jin; Rong Xiang; Liang-liang Fan; Ya-Li Li; Lei Zhu (Molecular Biology Reports, 2024)

PABPN1 functions as a predictive biomarker in colorectal carcinoma - Qing-hua Wang; Pei-ci Yan; Li-zhou Shi; Ya-jie Teng; Xiao-jiao Gao; Li-qian Yao; Zhi-wei Liang; Ming-hui Zhou; Wei Han; Rui Li (Molecular Biology Reports, 2024)

Notes on two new species of Russula subsect. Cyanoxanthinae (Russulaceae, Russulales) from southern China - Yan-Liu Chen; Jun-Feng Liang; Sheng-Kun Wang; Bin Chen; Jin-Hua Zhang; Meng-Ya An; Xing Li; Xue-Lian Gao; Xia Chen; Jin-Peng Liao (Mycological Progress, 2024)

Optical fiber fluorescence Cu2+ sensing technology based on CdSe/ZnS quantum dots: Large detection range, low detection limit - Ya-nan Zhang; Wenchao Liang; Like Li; Hongrui Zhang; Shangwen Cao; Bo Han; Yong Zhao (Analytica Chimica Acta, 2024)

Optimal operation of CCHP system with duality operation strategy considering hydrogen trading and carbon capture - Zhi-Feng Liu; Ya-He Huang; Qing Kang; Ze-Qi Li; Jing Lu; Rui-Zheng Gu; Xing-Fu Luo; Xiao-Rui Chen; You-Yuan Liu; Yu Tang; Liang Guo (Sustainable Cities and Society, 2024)

Application and innovation of artificial intelligence models in wastewater treatment - Wen-Long Xu; Ya-Jun Wang; Yi-Tong Wang; Jun-Guo Li; Ya-Nan Zeng; Hua-Wei Guo; Huan Liu; Kai-Li Dong; Liang-Yi Zhang (Journal of Contaminant Hydrology, 2024)

Estimation of Regional Evapotranspiration Based on the Decouple Model and Remote Sensing Information ——a Case Study in Beijing City and Nearby Region - Su-Chuang Di; Zhao-Liang Li; Yanmin Ren; Meng Liu; Ya-Zhen Jiang; Fan-Dong Zheng; Xue-Min Li; Yan-Bing Qi; Hong-Lu Liu; Ronglin Tang (International Journal of Remote Sensing, 2024)

The LINGO-1-deficient neural stem cell-derived neural tissueoid showed enhanced retention and neuronal relay in the transected spinal cord - Ge Li; Li-Jun Huang; Bao Zhang; Shu Liu; Jing-Hua Liang; Ying Ding; Xiang Zeng; Bi-Qin Lai; Yuan-Huan Ma; Ya-Qiong Wang; Rui Wang; Hong-Bo Zhang; et al. (Chemical Engineering Journal, 2024)

Efficient and low-cost Ni-NiO/Al2O3 catalysts with dual-active-sites for selective catalytic conversion of phthalic anhydride to phthalide - Liang-Liang Zhang; Xiao-Min Duan; Kai-Xuan Yang; Yu-Bo Xu; Jia-Ping Lu; Wan-Xi Li; Bo-Qiong Li; Cai-Long Xue; Ya-Jie Liu (Chemical Engineering Journal, 2024)

Prevalence and molecular characteristics of intestinal pathogenic Escherichia coli isolated from diarrheal pigs in Southern China - Qian Li; Jing-Jing Dai; Shu-Yi Chen; Ruan-Yang Sun; Dong Wang; Shuan-Cheng Bai; Min-Ge Wang; Jian Sun; Xiao-Ping Liao; Ya-Hong Liu; Liang-Xing Fang (Veterinary Microbiology, 2024)

Precipitation patterns impact soil aggregates and organic carbon of an alpine wetland on the Qinghai-Tibetan Plateau - Qian-Wei Li; Xiao-Ya Zhang; Jun-Qin Gao; Riikka Rinnan; Yi Jiao; Jin-Feng Liang; Fei-Hai Yu (CATENA, 2024)

Comprehensive analyses show the enhancement effect of exogenous melatonin on fluroxypyr-meptyl multiple phase metabolisms in Oryza sativa for reducing environmental risks - Zhao Jie Chen; Si Ying Li; Ya Nan Qu; Gan Ai; Yan Hui Wang; Dong Jin Pan; Hao Wen Wang; Dan Lu; Xiao Liang Liu (Pesticide Biochemistry and Physiology, 2024)

MOF-derived CoP/C catalyst for efficient dibenzothiophene hydrodesulfurization - Liang-Liang Zhang; Kai-Xuan Yang; Cai-Long Xue; Wan-Xi Li; Bo-Qiong Li; Yi-En Du; Yong-Qiang Chen; Ya-Jie Liu (Fuel, 2024)

Electrocatalytic nitrogen reduction to ammonia at low overpotentials based on tungsten carbide doped by non-precious metal single cobalt atoms - Ya Gao; Meng-Jiao Zhu; Xian-He Liu; Guo-Liang Dai; Yi-Wen Zhou; Ze-Da Meng; Li Luo; Tian Gan; Feng Chen; Yu-Yang Zhou; Wen-Wen Deng; Shou-Qing Liu (Chemical Engineering Journal, 2024)

Evolutionary and functional analysis of metabotropic glutamate receptors in lampreys - Ruyu Zhuang; Zihao Yan; Yicheng Gao; Ayqeqan Nurmamat; Shuyuan Zhang; Min Xiu; Yuesi Zhou; Ya Pang; Ding Li; Liang Zhao; Xin Liu; Yinglun Han (Fish Physiology and Biochemistry, 2024)

Development of the near-infrared fluorescence probe for detection of ONOO− and its application in vitro and vivo - Ya-Jing Shang; Yuan-Yuan Li; Jia-Ling Hu; Yi-Ru Wang; Sheng-Tao Li; Xing-Hu Wu; Ai-Hong Zhang; Yu-Wei Tan; Ting Liang; Xiao-Bo Zhu; Yan-Fei Kang (Analytica Chimica Acta, 2024)

Niche convergence and biogeographic history shape elevational tree community assembly in a subtropical mountain forest - Liang-Liang Ma; Sebastian Seibold; Marc W. Cadotte; Jia-Yun Zou; Jie Song; Zhi-Qiong Mo; Shao-Lin Tan; Lin-Jiang Ye; Wei Zheng; Kevin S. Burgess; Zhi-Fa Chen; De-Tuan Liu; et al. (Science of The Total Environment, 2024)

Evolution of physicochemical and leaching characteristics of municipal solid waste incineration fly ash in China under ultra-low emission standard - Guangyuan Yao; Rongbin Xu; Zhu Liang; Ping Li; Ya Xu; Yuqiang Liu; Can Qian; Qifei Huang (Journal of Environmental Management, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Parent material influences soil properties to shape bacterial community assembly processes, diversity, and enzyme-related functions - Yu-Zhu Li; Xue-Lian Bao; Xue-Feng Zhu; Fang-Bo Deng; Ya-Li Yang; Yue Zhao; Hong-Tu Xie; Shi-Xin Tang; Cheng-Jun Ge; Chao Liang (Science of The Total Environment, 2024)

Research on the screening and inhibition mechanism of angiotensin I-converting enzyme (ACE) inhibitory peptides from tuna dark muscle - Xin-Yu Zu; Ya-Nan Zhao; Yan Liang; Ying-Qiu Li; Chen-Ying Wang; Xiang-Zhong Zhao; Hua Wang (Food Bioscience, 2024)

Identifying modifiable factors and their joint effect on brain health: an exposome-wide association study - Liang-Yu Huang; Yi-Jun Ge; Yan Fu; Yong-Li Zhao; Ya-Nan Ou; Yi Zhang; Ling-Zhi Ma; Shi-Dong Chen; Ze-Xin Guo; Jian-Feng Feng; Wei Cheng; Lan Tan; et al. (GeroScience, 2024)

Spatio-temporal patterns of intense tropical cyclones in the Western North Pacific over the past 1600 years - Liang Zhou; Rumeng Hao; Mingchen Li; Yan Su; Shu Gao; Yang Yang; Zhixiong Shen; Jianjun Jia; Ya Ping Wang (Marine Geology, 2024)

Vertical migration behavior simulation and prediction of Pb and Cd in co-contaminated soil around Pb-Zn smelting slag site - Ying Luo; Zhe Wang; Yong-De Zhang; Jia-Qian Zhang; Qiu-ping Zeng; Zhen-Long Zhang; Duan Tian; Chao Li; Chao-liang Peng; Kai Ye; Yi-Ming Chen; Feng-Yu Huang; et al. (Journal of Hazardous Materials, 2024)

IRE1α: from the function to the potential therapeutic target in atherosclerosis - Zheng-Yang Zhou; Li Wu; Yi-Fan Liu; Mu-Yao Tang; Jing-Yi Tang; Ya-Qian Deng; Lei Liu; Bin-Bin Nie; Zi-Kai Zou; Liang Huang (Molecular and Cellular Biochemistry, 2024)

Eudesmane sesquiterpenoids with inhibitory effects on NO production from Artemisia princeps - Hong-Xia Li; Ning Diao; Ya-Jie Hu; Su-Juan Wang; Dong Liang; Gui-Jie Zhang (Phytochemistry, 2024)

Phylogenomic analyses sheds new light on the phylogeny and diversification of Corydalis DC. in Himalaya–Hengduan Mountains and adjacent regions - Yan-Yan Liu; Jia-Liang Cao; Sheng-Long Kan; Peng-Hang Wang; Jun-Li Wang; Ya-Nan Cao; Hong-Wei Wang; Jia-Mei Li (Molecular Phylogenetics and Evolution, 2024)

PM2.5 exposure-induced senescence-associated secretory phenotype in airway smooth muscle cells contributes to airway remodeling - Pei-Pei Cheng; Fan Yu; Shuai-Jun Chen; Xiao Feng; Zi-Heng Jia; Shi-He Hu; Xiao-Lin Cui; Ya-Ya Zhou; Qian Niu; Li-Mei Liang; Meng Wang; Lin-Jie Song; et al. (Environmental Pollution, 2024)

A human-specific insertion promotes cell proliferation and migration by enhancing TBC1D8B expression - Hui Zhao; Lin-Lin Liu; Jian Sun; Lian Jin; Hai-Bing Xie; Jian-Bo Li; Hui Xu; Dong-Dong Wu; Xiao-Lin Zhuang; Min-Sheng Peng; Ya-Jun Guo; Wei-Zhu Qian; et al. (Science China Life Sciences, 2024)

HMGB1 Mediates Inflammation-Induced DMT1 Increase and Dopaminergic Neurodegeneration in the Early Stage of Parkinsonism - Tuo Liang; Sheng-Xi Yang; Christopher Qian; Li-Da Du; Zhong-Ming Qian; Wing-Ho Yung; Ya Ke (Molecular Neurobiology, 2024)

Inflammatory cell death PANoptosis is induced by the anti-cancer curaxin CBL0137 via eliciting the assembly of ZBP1-associated PANoptosome - Ya-Ping Li; Zhi-Ya Zhou; Liang Yan; Yi-Ping You; Hua-Yu Ke; Tao Yuan; Hai-Yan Yang; Rong Xu; Li-Hui Xu; Dong-Yun Ouyang; Qing-Bing Zha; Xian-Hui He (Inflammation Research, 2024)

Effects of lianas on forest biogeochemistry during their lives and afterlives - Gbadamassi G. O. Dossa; Hong‐Lin Li; Bo Pan; Tial C. Ling; Douglas A. Schaefer; Mareike Roeder; Denis M. Njoroge; Juan Zuo; Liang Song; Bismark Ofosu‐Bamfo; Stefan A. Schnitzer; Rhett D. Harrison; et al. (Global Change Biology, 2024)
Climate change and other anthropogenic disturbances are increasing liana abundance and biomass in many tropical and subtropical forests. While the effects of living lianas on species diversity, ecosystem carbon, and nutrient dynamics are receiving increasing attention, the role of dead lianas in forest ecosystems has been little studied and is poorly understood. Trees and lianas coexist as the major woody components of forests worldwide, but they have very different ecological strategies, with lianas relying on trees for mechanical support. Consequently, trees and lianas have evolved highly divergent stem, leaf, and root traits. Here we show that this trait divergence is likely to persist after death, into the afterlives of these organs, leading to divergent effects on forest biogeochemistry. We introduce a conceptual framework combining horizontal, vertical, and time dimensions for the effects of liana proliferation and liana tissue decomposition on ecosystem carbon and nutrient cycling. We propose a series of empirical studies comparing traits between lianas and trees to answer questions concerning the influence of trait afterlives on the decomposability of liana and tree organs. Such studies will increase our understanding of the contribution of lianas to terrestrial biogeochemical cycling, and help predict the effects of their increasing abundance.

Mogroside V alleviates the heat stress-induced disruption of the porcine oocyte in vitro maturation - Ke Peng; Kexin Cui; Pan Li; Xinxin Liu; Ya Du; Huiyan Xu; Xiaogan Yang; Shengsheng Lu; Xingwei Liang (Theriogenology, 2024)

Removal of Bismuth from Water by Orange Peel Biochar - Adil Abbas Kareem; Yu-liang Liao; Ya-qi Yu; Ning Ning; Shan-shan Guo; Qiao-yu Song; Jia-li Li; Jin-yan Yang (Water, Air, & Soil Pollution, 2024)

Potential protective effects of sodium butyrate on glycinin-induced oxidative stress, inflammatory response, and growth inhibition in Cyprinus carpio - Deng-Lai Li; Si-Ying Liu; Rui Zhu; Si-Tong Meng; Yin-Tao Wang; Zhi-Yong Yang; Liang Li; Xiao-Fang Wei; Guo-Jun Shang; Hao-Tong Wang; Zi-Hui Qu; Ya-Nan Quan; et al. (Fish Physiology and Biochemistry, 2024)

Adaptive evolution in asymptomatic host confers MDR Salmonella with enhanced environmental persistence and virulence - Bing He; Ting-ting Zhu; Yin Liang; Hai-jing Wei; Zi-lei Huang; Li-jie Liang; Jia-hao Zhong; Yang Luo; Xin-lei Lian; Dong-hao Zhao; Xiao-ping Liao; Ya-hong Liu; et al. (Science of The Total Environment, 2024)

Effects of sub-chronic exposure to microcystin-LR on the endocrine system of male rats - Yu-Ting Wang; Qian-Hui Wu; Liang Chen; John P. Giesy; Lin-Lin Xu; Wen-Li Xu; Jun He; Ting Shi; Yi-Qing Liu; Shi-Man Xiao; Ye-Ke Wang; Feng Chen; et al. (Science of The Total Environment, 2024)

Unlocking the potential of N-acetylcysteine: Improving hepatopancreas inflammation, antioxidant capacity and health in common carp (Cyprinus carpio) via the MAPK/NF-κB/Nrf2 signalling pathway - Rui Zhu; Guo-Jun Shang; Bao-Yuan Zhang; Hao-Tong Wang; Liang Li; Xiao-fang Wei; Deng-Lai Li; Zhi-Yong Yang; Zi-Hui Qu; Ya-Nan Quan; Si-Ying Liu; Yin-Tao Wang; et al. (Fish & Shellfish Immunology, 2024)

Urban green, blue spaces and their joint effect are associated with lower risk of emotional and behavior problem in children and adolescents, a large population-based study in Guangzhou, China - Jing-hong Liang; Ru-yu Yang; Mei-ling Liu; Ying-qi Pu; Wen-wen Bao; Yu Zhao; Li-xin Hu; Yu-shan Zhang; Shan Huang; Nan Jiang; Xue-ya Pu; Shao-yi Huang; et al. (Environmental Research, 2024)

Fructooligosaccharides and fructans from Platycodon grandiflorum: Structural characterization, lung-oriented guidance and targetability - Jun Liang; Wen-Fei Wang; Yi Zhang; Yan-Qun Chai; Ya-Ge Li; Si-Liang Jiang; Xin-Hua Zhu; Yu-Li Guo; Zhen Wei; Xi-Zhe Sun; Hai-Xue Kuang; Yong-Gang Xia (Carbohydrate Polymers, 2024)

Uptake, translocation, accumulation, and metabolism of fluroxypyr-meptyl and oxidative stress induction in rice seedling - Zhao Jie Chen; Hao Wen Wang; Si Ying Li; Yong Heng Zhang; Ya Nan Qu; Zhi Hai He; Xue Sheng Li; Xiao Liang Liu (Environmental Science and Pollution Research, 2023)

Physiological and biochemical changes in leaf abscission of Cyclocarya paliurus stem segments in vitro - Qiu-Ying Li; Shuang Wang; Gao-Yin Wu; Ya Tan; Ying-Ying Liu; Cong-Jun Yuan; Shuang-Gui Geng; Ying-Liang Liu (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Salidroside Ameliorates Ischemia/Reperfusion-Induced Human Cardiomyocyte Injury by Inhibiting the Circ_0097682/miR-671-5p/USP46 Pathway - Yuyang Yang; Fangqian Liang; Jingyuan Gao; Jian Li; Chunhua Jiang; Wei Xie; Shujuan Wu; Ya Wang; Jing Yi (Cardiovascular Toxicology, 2023)

Triptolide induces PANoptosis in macrophages and causes organ injury in mice - Hong-Rui Zhang; Ya-Ping Li; Zi-Jian Shi; Qi-Qi Liang; Si-Yuan Chen; Yi-Ping You; Tao Yuan; Rong Xu; Li-Hui Xu; Dong-Yun Ouyang; Qing-Bing Zha; Xian-Hui He (Apoptosis, 2023)

An electrochemical aptasensor for detection of carbofuran using gold nanoparticles decorated hierarchical porous carbon as an effective sensing platform - Lihong Luo; Cuiwen Jiang; Hu Li; Dejiao Ning; Shuibing Lao; Zhongdan Liang; Li Tang; Weiwei Chen; Yu Ya (Chemosphere, 2023)

Geographical and morphological changes of conifers in Yunnan, China during the Cenozoic in response to climatic changes - Jian-Wei Zhang; Ashalata D'Rozario; Li Wang; Jian Huang; Ya Li; Xiao-Qing Liang; Zhe-Kun Zhou (Review of Palaeobotany and Palynology, 2023)

Synergistic impact of co-exposures to whole blood metals on chronic kidney disease in general US adults: a cross‑sectional study of the National Health and Nutrition Examination Survey 2011–2020 - Jing-hong Liang; Ying-qi Pu; Mei-ling Liu; Wen-wen Bao; Yu-shan Zhang; Li-xin Hu; Shan Huang; Nan Jiang; Shao-yi Huang; Xue-ya Pu; Guang-hui Dong; Ya-jun Chen (Environmental Science and Pollution Research, 2023)

Bioactivities of thymol and p-cymene from the essential oil of Adenosma buchneroides against three stored-product insects - Qiao-Hui Xie; Tian-Liang; Bo-Ya Li; Jiao-Neng Yu; Yu Zheng; Shu-Shan Du; Almaz Borjigidai (Environmental Science and Pollution Research, 2023)

Environmental exposure and ecological risk of perfluorinated substances (PFASs) in the Shaying River Basin, China - Ya-Hui Zhang; Ting-Ting Ding; Zi-Yan Huang; Hong-Yi Liang; Shi-Lin Du; Jin Zhang; Hui-Xian Li (Chemosphere, 2023)

Prospects and perspectives on advanced materials for sodium-ion batteries - Zhen-Yi Gu; Xiao-Tong Wang; Yong-Li Heng; Kai-Yang Zhang; Hao-Jie Liang; Jia-Lin Yang; Edison Huixiang Ang; Peng-Fei Wang; Ya You; Fei Du; Xing-Long Wu (Science Bulletin, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Undescribed steroidal alkaloids from the bulbs of Fritillaria sinica - Jia-yuan Li; Shi-fei Wu; Ya-ling An; Chang-liang Yao; Shuai Yao; Yong Huang; Wen-long Wei; Jian-qing Zhang; Qi-rui Bi; Hua Qu; De-an Guo (Phytochemistry, 2023)

“Mini-community” simulation revealed the differences of endophytic fungal communities between the above- and below-ground tissues of Ephedra sinica Stapf - Xi Liu; Jin-Long Cui; Zhong-Ya Zhou; Zong-Bao Zhang; Xuan-Ge Cui; Bo Han; Jun-Hong Wang; Meng-Liang Wang; Yi-Min Li (Fungal Biology, 2023)

Microplastics cause reproductive toxicity in male mice through inducing apoptosis of spermatogenic cells via p53 signaling - Chunsheng Lu; Yuehui Liang; Ya Cheng; Chan Peng; Yuanyuan Sun; Kangle Liu; Yingqing Li; Yixia Lou; Xiao Jiang; Aihua Zhang; Jinyi Liu; Jia Cao; et al. (Food and Chemical Toxicology, 2023)

Allelopathy of p-coumaric acid on Limnothrix sp., a bloom-forming cyanobacteria - Liping Wu; Lingzhi Li; Pan Dong; Liang Zhang; Hui Tang; Ya Han; Gengxin Xie (Algal Research, 2023)

Joint effect of whole blood metals exposure with dyslipidemia in representative US adults in NHANES 2011–2020 - Jing-hong Liang; Ying-qi Pu; Mei-ling Liu; Li-xin Hu; Wen-wen Bao; Yu-shan Zhang; Aerziguli Kakaer; Yu Zhao; Yi-can Chen; Xue-ya Pu; Shao-yi Huang; Nan Jiang; et al. (Environmental Science and Pollution Research, 2023)

TiO2 nanoparticles affect spermatogenesis and adhesion junctions via the ROS-mediated mTOR signalling pathway in Eriocheir sinensis testes - Lan-Min Wang; Ke Jia; Zhen-Fang Li; Hong-Yu Qi; Ding-Xi Liu; Ya-Jing Liang; Shuang-Li Hao; Fu-Qing Tan; Wan-Xi Yang (Environmental Pollution, 2023)

Quantitative analysis and survey of 9,10-anthraquinone contaminant in Chinese Liupao tea - Jianfeng Liang; Ya Li; Yuejing Bin; Ruying Qiao; Lijian Ke; Shuiqiao Zhong; Yanni Liang (Food Additives & Contaminants: Part A, 2023)

Benfotiamine attenuates the high-carbohydrate diet-induced mitochondrial redox imbalance in fish Megalobrama amblycephala by activating SIRT3 - Ling Zhang; Ya-Ping Ge; Yang-Yang Huang; Wei-Liang Chen; Wen-Bin Liu; Ding-Dong Zhang; Xiang-Fei Li (Aquaculture, 2023)

Indoxyl sulfate in atherosclerosis - Cong Lu; Li Wu; Mu-Yao Tang; Yi-Fan Liu; Lei Liu; Xi-Ya Liu; Chun Zhang; Liang Huang (Toxicology Letters, 2023)

Novel biological nitrogen removal process for the treatment of wastewater with low carbon to nitrogen ratio: A review - Kaiyao Hu; Wenxuan Li; Yaning Wang; Bo Wang; Hao Mu; Shuang Ren; Kexin Zeng; Hongjuan Zhu; Jinming Liang; Ya'e Wang; Juqiang Xiao (Journal of Water Process Engineering, 2023)

Mechanism of polycyclic aromatic hydrocarbons degradation in the rhizosphere of Phragmites australis: Organic acid co-metabolism, iron-driven, and microbial response - Ni-chen Zhang; Dan A; Yuan-qing Chao; Hai-Yan Li; Charles Li; Qing-qi Lin; Ya-ying Li; Rong-liang Qiu (Environmental Pollution, 2023)

Perfluorooctane sulfonate and perfluorooctanoic acid inhibit progesterone-responsive capacitation through cAMP/PKA signaling pathway and induce DNA damage in human sperm - Lijun Shan; Yuhao Chai; Tian Gao; Kun Li; Jianmin Yu; Fei Liang; Ya Ni; Peibei Sun (Environmental Toxicology and Pharmacology, 2023)

Pulsed counterclockwise rotation of the southwestern Sichuan Basin in response to the India-Asia convergence during 128-42 Ma - Qi Shen; Chun-Sheng Jin; Wen-Tian Liang; Chuan-Zhi Li; Hui-Hui Yang; Ya-Zhou Ran; Xuan He; Guan-Zuo Wu; Kai Jiang; Jian-Gang Li; Peng Han; Si-Hua Yuan (Earth and Planetary Science Letters, 2023)

Unravelling the role of reactive oxygen species in ultrathin Z-scheme heterojunction with surface zinc vacancies for photocatalytic H2O2 generation and CTC degradation - Hui-Yun Liu; Cheng-Gang Niu; Da-Wei Huang; Chao Liang; Hai Guo; Ya-Ya Yang; Lu Li (Chemical Engineering Journal, 2023)

Challenges in DIC measurement of segregation frost heave and its solutions by adaptive updating algorithm - Meng Wang; Xu Li; Yu-zhi Zhang; Yan-liang Du; Zhen-ya Liu; Dong Zhang (Cold Regions Science and Technology, 2023)

The Synergistic Activity and Interaction Mechanism of Linoleic Acid and a Bioactive Pentapeptide (Tyr-Val-Pro-His-Trp) from Walnut Meal in the Treatment of Alzheimer’s Disease - Zi-Chun Wang; Yu-Xi Ling; Ya-Xin Liang; Zi-Qi Li; Jie Dai; Di-Feng Ren (International Journal of Peptide Research and Therapeutics, 2023)

Colonic mechanism of serum NAD+ depletion induced by DEHP during pregnancy - Yun Hong; Xia Ning; Yue-yue Liang; Xiao-lu Li; Ya Cui; Wei Wu; Yang Cai; Shuai Zhao; Meng Zhu; Tian-xiao Zhong; Hua Wang; De-xiang Xu; et al. (Science of The Total Environment, 2023)

Heavy metals in riverine/estuarine sediments from an aquaculture wetland in metropolitan areas, China: Characterization, bioavailability and probabilistic ecological risk - Hai-Song Li; Yang-Guang Gu; Rui-Ze Liang; Ya-Su Wang; Richard W. Jordan; Liang-Gen Wang; Shi-Jun Jiang (Environmental Pollution, 2023)

Rolling flexible double-MXenes TiCT/VCT hybrid films for microsupercapacitors - Shuaikai Xu; Hongpeng Yang; Yubing Li; Haifu Huang; Xianqing Liang; Yuanhao Wang; Qing Hu; Guodong Wei; Ya Yang (Chemical Engineering Journal, 2023)

The effect of phthalates exposure during pregnancy on asthma in infants aged 0 to 36 months: a birth cohort study - Jian-Qing Wang; Chun-Mei Liang; Ya-Bin Hu; Xun Xia; Zhi-Juan Li; Hui Gao; Jie Sheng; Kun Huang; Su-Fang Wang; Peng Zhu; Jia-Hu Hao; Fang-Biao Tao (Environmental Geochemistry and Health, 2023)

Triassic igneous activities in the east flank of the East Kunlun orogenic belt: the Daheba complex example - Nan Tian; Feng-Yue Sun; Zhong-Cui Pan; Liang Li; Yan Gu; Dong-Qian Wu; Jia-Fang Deng; Zhe-Dong Liu; Li Wang; Ya-Jing Zhang (International Geology Review, 2023)

Punctiform Breakup and Initial Oceanization in the Central Red Sea Rift - Ya-Di Sang; Bakhit M. T. Adam; Chun-Feng Li; Liang Huang; Yong-Lin Wen; Jia-Ling Zhang; Yu-Tao Liu (Journal of Marine Science and Engineering, 2023)
The Central Red Sea Rift is a natural laboratory to study the transition from rifting to spreading. Based on new reflection seismic profiles and gravity modeling, we examined the crustal structure, tectonic evolution, breakup mechanism, and future evolution of the Central Red Sea Rift. Along this rift axis, the breakup of continental lithosphere is discontinuous and the oceanic crust is limited to the axial deeps. The punctiform breakup and formation of deeps is assisted by mantle upwelling and topographic uplift, but the nucleation is directly controlled by the normal-fault system. The discontinuities spaced between axial deeps within the relatively continuous central troughs are presently axial domes or highs and will evolve into new deeps with tectonic subsidence. Isolated deeps will grow and connect with each other to become a continuous central trough, before transitioning into a unified spreading center.

High-efficient fire-safe epoxy enabled by bio-based atomic-level catalytic engineering - Lin-Yun Jiang; Zhi Li; Ya-Min Liang; Qing-Qing Bi; Song Tian; Shao-Yu Lin; Zhi Hu; Yu Zheng; Jose Hobson; De-Yi Wang (Chemical Engineering Journal, 2023)

Effective Removal of Aqueous Cu(II) Pollution by a Novel Readily Prepared Porous Biomaterial Using Crab Shell Wastes - Ya-Ming Ge; Liang Zhang; Yong Zhang; Jia-Shun Yang; Hui-Min Gao; Shi-Jie Li; Jun-Zhi Liu (Water, Air, & Soil Pollution, 2023)

The potential mechanism of Neu5Gc inducing colorectal cancer based on network pharmacology and experimental validation - Li-Chao Zhang; Ya-Ning Liu; Xiao-Qin La; Shu-Ning Yan; Yu Chen; Jing-Yi Liang; Zhuo-Yu Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Grazing impairs ecosystem stability through changes in species asynchrony and stability rather than diversity across spatial scales in desert steppe, Northern China - Shanshan Sun; Shenglong Zhao; Xinping Liu; Peng Lv; Maowei Liang; Yulin Li; Ya Hu; Xiaoan Zuo (Agriculture, Ecosystems & Environment, 2023)

The diversity of mycorrhiza‐associated fungi and trees shapes subtropical mountain forest ecosystem functioning - Ya‐Huang Luo; Liang‐Liang Ma; Sebastian Seibold; Marc W. Cadotte; Kevin S. Burgess; Shao‐Lin Tan; Lin‐Jiang Ye; Wei Zheng; Jia‐Yun Zou; Zhi‐Fa Chen; De‐Tuan Liu; Guang‐Fu Zhu; et al. (Journal of Biogeography, 2023)
Aim Mycorrhiza play key roles for ecosystem structure and functioning in forests. However, how different mycorrhizal types influence mountain forest biodiversity–ecosystem functioning (BEF) relationships are largely unknown. We evaluate how the diversity of distinct mycorrhiza‐associated fungi and trees shapes forest carbon storage along elevational gradients. Location Gaoligong Mountains within Hengduan Mountains, Southwest China. Taxon Seed plants and mycorrhizal fungi. Methods We used the data from 31 subtropical forest plots along elevational gradients on two aspects (east and west) of the mountain. We quantified species richness of trees and symbiotic fungi and assigned both to their mycorrhizal type (arbuscular mycorrhiza [AM], ectomycorrhiza [EcM] and ericoid mycorrhiza [ErM]). We then examined the diversity effects of mycorrhiza‐associated fungi and trees on above‐ground carbon stored in trees and organic carbon stored in soils. Results Species richness was highest for AM trees (79.5%), followed by ErM trees (13.4%) and then EcM trees (7.1%). Species richness of AM‐associated trees and fungi decreased with increasing elevation, while ErM‐associated trees and fungi showed an opposite trend. EcM‐associated diversity followed a hump‐shaped relationship with elevation. Positive relationships between diversity and above‐ground carbon were detected in all three mycorrhizal associations, but despite low species number, canopy‐dominating EcM trees comprised 64.4% of the amount of above‐ground carbon. Furthermore, community‐weighted means of height exhibited positive correlations with forest above‐ground carbon, indicating that positive selection effects occur. Soil organic carbon was positively related to EcM‐associated fungi diversity, above‐ground carbon mass and soil nitrogen availability, with the latter having strongest direct effects. Main Conclusions The distributions of forest biodiversity and carbon storage can be modulated by distinct mycorrhizal fungi and trees. Moreover, future global changes (e.g. climate warming, intensifying nitrogen deposition) could alter the mycorrhizal‐mediated BEF relationships in mountain forests.

Potential of crop straw incorporation for replacing chemical fertilizer and reducing nutrient loss in Sichuan Province, China - Ying Wang; Bang-qiang Liang; Hui Bao; Qian Chen; Ya-lei Cao; Yan-qing He; Liang-zhong Li (Environmental Pollution, 2023)

First Asian fossil record of Platydictya (Amblystegiaceae) from the lower Miocene and its paleoenvironmental significance - Liyan Guo; Liang Xiao; Ya Li; Xiangchuan Li; Qin Leng; Nan Sun; Junfeng Guo; Chaofeng Fu; Jianan Wang; Deshuang Ji (Frontiers of Earth Science, 2023)

Rockburst and microseismic activity in a lagging tunnel as the spacing between twin TBM excavated tunnels changes: A case from the Neelum-Jhelum hydropower project - Peng-Xiang Li; Bing-Rui Chen; Ya-Xun Xiao; Guang-Liang Feng; Yang-Yi Zhou; Jin-Shuai Zhao (Tunnelling and Underground Space Technology, 2023)

ARSCP: An antimicrobial residue surveillance cloud platform for animal-derived foods - Jun-Jun Yu; Ya-Lin Hu; Cheng-Zheng Liu; Shuai-Bin Wu; Zi-Jian Zheng; Ze-Hua Cui; Li Chen; Tian Wei; Shi-Kai Sun; Jun Ning; Xiang Wen; Qiu-Yue Diao; et al. (Science of The Total Environment, 2023)

Resveratrol ameliorates the defects of meiotic maturation in lipopolysaccharide exposed porcine oocytes - Xinxin Liu; Pan Li; Ke Yan; Ya Du; Ke Peng; Mengqi Li; Kexin Cui; Hengye Zhang; Xiaogan Yang; Shengsheng Lu; Xingwei Liang (Reproductive Toxicology, 2023)

Variations in Asian summer monsoon and hydroclimate during Heinrich stadials 4 revealed by stalagmite stable isotopes and trace elements - Yao Wu; Ting-Yong Li; Jun-Yun Li; Hai Cheng; You-Feng Ning; Chuan-Chou Shen; Yan Yang; Jing-Yao Zhao; Chao-Jun Chen; Ming-Qiang Liang; Si-Ya Xiao; Hai-Ying Qiu; et al. (Quaternary Science Reviews, 2023)

Transforming growth factor-β signaling: From tissue fibrosis to therapeutic opportunities - Li-Li Ren; Xiao-Jun Li; Ting-Ting Duan; Zheng-Hai Li; Jun-Zheng Yang; Ya-Mei Zhang; Liang Zou; Hua Miao; Ying-Yong Zhao (Chemico-Biological Interactions, 2023)

Receptor and Ionic Mechanism of Histamine on Mouse Dorsolateral Striatal Neurons - Jian-Ya Peng; Kang-Li Shen; Xiu-Juan Fan; Zeng-Xin Qi; Hui-Wei Huang; Jian-Lan Jiang; Jian-Hua Lu; Xiao-Qin Wang; Xiao-Xia Fang; Wang-Rui Yuan; Qiao-Xuan Deng; Shu Chen; et al. (Molecular Neurobiology, 2023)

Expanding the valorization of waste mushroom substrates in agricultural production: progress and challenges - Ya Gao; Zhibin Wu; Weiming Li; Haibo Sun; Youzheng Chai; Tianyou Li; Chao Liu; Xiaomin Gong; Yunshan Liang; Pufeng Qin (Environmental Science and Pollution Research, 2023)

The landscape of aging - Yusheng Cai; Wei Song; Jiaming Li; Ying Jing; Chuqian Liang; Liyuan Zhang; Xia Zhang; Wenhui Zhang; Beibei Liu; Yongpan An; Jingyi Li; Baixue Tang; et al. (Science China Life Sciences, 2022)

Siccirubricoccus soli sp. nov., a novel bacterial species isolated from Jiaozi Mountain soil - Guo-Xing Zhu; Ya-Jie Wu; Yan-Ru Cao; Bing-Jun Fan; Yu Jiao; Xiu-Li Hou; Zi-Chao Liu; Yue Zhang; Jiang-Bo He; Lian-Ming Liang (Antonie van Leeuwenhoek, 2022)

Feed types affect the growth, nutrient utilization, digestive capabilities, and endocrine functions of Megalobrama amblycephala: a comparative study between pelleted and extruded feed - Chao-Fan He; Xiang-Fei Li; Guang-Zhen Jiang; Ling Zhang; Miao Sun; Ya-Ping Ge; Wei-Liang Chen; Wen-Bin Liu (Fish Physiology and Biochemistry, 2022)

Isolation and characterization of 112 SNP markers in Yellowfin seabream (Acanthopagrus latus) using RAD sequencing - Ke-Cheng Zhu; Ya-Ling Li; Wei-Bin Wu; Bao-Suo Liu; Hua-Yang Guo; Nan Zhang; Liang Guo; Dian-Chang Zhang (Conservation Genetics Resources, 2022)

Enhanced photosynthetic nitrogen use efficiency and increased nitrogen allocation to photosynthetic machinery under cotton domestication - Zhang-Ying Lei; Heng Wang; Ian J. Wright; Xin-Guang Zhu; Ülo Niinemets; Zi-Liang Li; Dong-Sheng Sun; Ning Dong; Wang-Feng Zhang; Zhong-Li Zhou; Fang Liu; Ya-Li Zhang (Photosynthesis Research, 2021)

Antimicrobial Natural Products Produced by Soil-Derived Fungus Penicillium cremeogriseum W1-1 - Xu-Yan Sang; Zhao-Jie Wang; Ya-Bin Yang; Yong-Liang Wang; Mei-Ling Xiang; Dou-Ying Zhu; Ying Zhou; Xiao-Dong Luo; Li-Xing Zhao (Indian Journal of Microbiology, 2021)

External evaluation of published population pharmacokinetic models of polymyxin B - Ya-qian Li; Kai-feng Chen; Jun-jie Ding; Hong-yi Tan; Nan Yang; Ya-qi Lin; Cui-fang Wu; Yue-liang Xie; Guo-ping Yang; Jing-Jing Liu; Qi Pei (European Journal of Clinical Pharmacology, 2021)

The chemical profile and biological activity of different extracts of Sapindus mukorossi Gaertn. against Cutibacterium acnes - Min-Ping Wei; Jin-Dan Qiu; Lu Li; Yun-Fei Xie; Ya-Hui Guo; Hang Yu; Yu-Liang Cheng; He Qian; Wei-Rong Yao (Natural Product Research, 2021)

Genetic and molecular characterization of determinant of six-rowed spike of barley carrying vrs1.a4 - Jin-Hui Wang; Zhen-Mei Xu; Xue-Bing Qiu; Li-Lan Li; Shui-Yang Yu; Tao Li; Yan-Yan Tang; Xi Pu; Juan-Yu Zhang; Hai-Li Zhang; Jun-Jun Liang; Ya-Wei Tang; et al. (Theoretical and Applied Genetics, 2021)

High nitrogen uptake and utilization contribute to the dominance of invasive Spartina alterniflora over native Phragmites australis - Qian-Wei Li; Xiao-Ya Zhang; Jin-Feng Liang; Jun-Qin Gao; Xing-Liang Xu; Fei-Hai Yu (Biology and Fertility of Soils, 2021)

Interaction of magnolia bark extracts with Staphylococcus aureus DNA and evaluation of the stability of their antibacterial activities - Shu-Mei Cui; Hai-yun Liang; Ting Li; Ke-Ke He; Yu-Mei Zheng; Meng Tang; Chong-rong Ke; Li-Ya Song (Archives of Microbiology, 2021)

Exploring the dynamic mechanism of allosteric drug SHP099 inhibiting SHP2E69K - Shan Du; Xin-hua Lu; Wei-Ya Li; Li-Peng Li; Yang-Chun Ma; Liang Zhou; Jing-Wei Wu; Ying Ma; Run-Ling Wang (Molecular Diversity, 2021)

Isolation and Identification of Pseudomonas sp. Strain DY-1 from Agricultural Soil and Its Degradation Effect on Prometryne - Dong Liang; Ming-yue Ding; Chang-yixin Xiao; Ya-wen Shen; Yin-yue Wang; Hai-tao Li; Rong-mei Liu; Ji-guo Gao (Current Microbiology, 2021)

Aluminum and magnesium status during pregnancy and placenta oxidative stress and inflammatory mRNA expression: China Ma’anshan birth cohort study - Jian-Qing Wang; Ya-Bin Hu; Chun-Mei Liang; Xun Xia; Zhi-Juan Li; Hui Gao; Jie Sheng; Kun Huang; Su-Fang Wang; Yan Li; Peng Zhu; Jia-Hu Hao; et al. (Environmental Geochemistry and Health, 2020)

Comparative iTRAQ Proteomics Reveals Multiple Effects of Selenium Yeast on Dairy Cows in Parturition - Zhi-hua Ren; Li-peng Bai; Liu-hong Shen; Zheng-zhong Luo; Zi-han Zhou; Zhi-cai Zuo; Xiao-ping Ma; Jun-liang Deng; Ya Wang; Sheng-yu Xu; Yu-heng Luo; Sui-zhong Cao; et al. (Biological Trace Element Research, 2020)

Constraints of salinity- and sediment-induced stratification on the turbidity maximum in a tidal estuary - Ting Lu; Hao Wu; Fan Zhang; Jiasheng Li; Liang Zhou; Jianjun Jia; Zhanhai Li; Ya Ping Wang (Geo-Marine Letters, 2020)

Macrophage–NLRP3 Inflammasome Activation Exacerbates Cardiac Dysfunction after Ischemic Stroke in a Mouse Model of Diabetes - Hong-Bin Lin; Guan-Shan Wei; Feng-Xian Li; Wen-Jing Guo; Pu Hong; Ya-Qian Weng; Qian-Qian Zhang; Shi-Yuan Xu; Wen-Bin Liang; Zhi-Jian You; Hong-Fei Zhang (Neuroscience Bulletin, 2020)

Nitric Oxide Negatively Regulates Larval Metamorphosis in Hard-Shelled Mussel (Mytilus coruscus) - You-Ting Zhu; Ya Zhang; Yu-Zhu Liu; Yi-Feng Li; Asami Yoshida; Kiyoshi Osatomi; Jin-Long Yang; Xiao Liang (Frontiers in Marine Science, 2020)

Anti-hypertensive effects of Radix Rehmanniae and its active ingredients - Chiu-Haw Chao; Jue-Liang Hsu; Mu-Fen Chen; Ya-Hu Shih; Chia-Hui Lee; Mei-Li Wu; Chi-I Chang (Natural Product Research, 2020)

Antibacterial Effects of Schisandra chinensis Extract on Escherichia coli and its Applications in Cosmetic - S. Mei Cui; T. Li; Q. Wang; K. Ke He; Y. Mei Zheng; H. Yun Liang; L. Ya Song (Current Microbiology, 2020)

Laboratory investigation of the mechanical properties of coal-rock combined body - Zhan-bo Cheng; Liang-Hui Li; Ya-Ning Zhang (Bulletin of Engineering Geology and the Environment, 2020)

Correction to: Vertical Distributions of Suspended Sediment Concentrations in the Turbidity Maximum Zone of the Periodically and Partially Stratified Changjiang Estuary - Zhanhai Li; Jianjun Jia; Yongsheng Wu; Haibo Zong; Guoan Zhang; Ya Ping Wang; Yang Yang; Liang Zhou; Shu Gao (Estuaries and Coasts, 2019)

Performance and Spatial Distribution of Functional Bacteria under Low-Temperature Stress in Biofilm Systems for Polluted Source Water Pretreatment - Guang-feng Yang; Li-juan Feng; Jun Mu; Jing-ya Sun; Liang Zhu; Xiang-yang Xu (International Journal of Environmental Research, 2019)

Influence of Different Propulsion Speeds on the Characteristics of Mine Pressure in the Fully Mechanized Caving Face During Rotary Stage - Liang Li; Xue He; Yong-qiang Chen; Ya-chun Li; Chen-hao Shi; Yu-ping Zhu (Geotechnical and Geological Engineering, 2019)

High genetic diversity and recombination events of porcine astrovirus strains identified from ill and asymptomatic pigs in 2017, Hunan Province, China - Sun-Liang Lv; Hui-Hui Zhang; Jie-Yu Li; Wen-Qin Hu; Ya-Ting Song; Tanja Opriessnig; Chao-Ting Xiao (Virus Genes, 2019)

Effect of Interaction between Adenosine and Nitric Oxide on Central Nervous System Oxygen Toxicity - Cheng-wei Xie; Zhong-zhuang Wang; Ya-nan Zhang; Yu-liang Chen; Run-ping Li; Jun-dong Zhang (Neurotoxicity Research, 2019)

Antifungal Susceptibility Profile of Candida Albicans Isolated from Vulvovaginal Candidiasis in Xinjiang Province of China - Liang Yan; Xiao-dong Wang; Seyedmojtaba Seyedmousavi; Juan-na Yuan; Palida Abulize; Wei-hua Pan; Nong Yu; Ya-li Yang; Hai-qing Hu; Wan-qing Liao; Shu-wen Deng (Mycopathologia, 2019)

Transport Dynamics of Mercury in Rainfall-runoff After Summer Drought in a Small Agricultural Watershed in the Three Gorges Reservoir Region - Qinqin Xu; Cheng Zhang; Li Liang; Dingyong Wang; Zheng Zhao; Ya Wang; Yongmin Wang (Bulletin of Environmental Contamination and Toxicology, 2019)

Effects of UV-B radiation on the survival, egg hatchability and transcript expression of antioxidant enzymes in a high-temperature adapted strain of Neoseiulus barkeri - Chuan-Bei Tian; Ya-Ying Li; Xian Wang; Wen-Hui Fan; Ge Wang; Jing-Yu Liang; Zi-Ying Wang; Huai Liu (Experimental and Applied Acarology, 2019)

A bioactive new protostane-type triterpenoid from Alisma plantago - aquatica subsp. orientale (Sam.) Sam. - Ya-Li Wang; Jian-Chao Zhao; Jia-Hao Liang; Xiang-Ge Tian; Xiao-Kui Huo; Lei Feng; Jing Ning; Chao Wang; Bao-Jing Zhang; Gang Chen; Ning Li; Cheng-Peng Sun (Natural Product Research, 2019)

Drought loss assessment combining remote sensing and a crop growth model for maize in Yunnan Province, China - Maofang Gao; Zhao-Liang Li; Sanchao Liu; Ya Gao; Pei Leng; Sibo Duan (International Journal of Remote Sensing, 2019)

Chronic Intracerebroventricular Infusion of Metformin Inhibits Salt-Sensitive Hypertension via Attenuation of Oxidative Stress and Neurohormonal Excitation in Rat Paraventricular Nucleus - Xiao-Jing Yu; Ya-Nan Zhao; Yi-Kang Hou; Hong-Bao Li; Wen-Jie Xia; Hong-Li Gao; Kai-Li Liu; Qing Su; Hui-Yu Yang; Bin Liang; Wen-Sheng Chen; Wei Cui; et al. (Neuroscience Bulletin, 2019)

Geomorphic features of Quaternary glaciation in the Taniantaweng Mountain, on the southeastern Qinghai-Tibet Plateau - Wei Zhang; Le Chai; Ian S Evans; Liang Liu; Ya-peng Li; Jing-ru Qiao; Qian-yu Tang; Bo Sun (Journal of Mountain Science, 2019)

Frond transformation system mediated by Agrobacterium tumefaciens for Lemna minor - Gui-Li Yang; Yang Fang; Ya-Liang Xu; Li Tan; Qi Li; Yang Liu; Fan Lai; Yan-Ling Jin; An-Ping Du; Kai-Ze He; Xin-Rong Ma; Hai Zhao (Plant Molecular Biology, 2018)

Preference and performance of the two-spotted spider mite Tetranychus urticae (Acari: Tetranychidae) on strawberry cultivars - Ya-Jun Gong; Jin-Cui Chen; Liang Zhu; Li-Jun Cao; Gui-Hua Jin; Ary A. Hoffmann; Chuan-Fei Zhong; Peng Wang; George Lin; Shu-Jun Wei (Experimental and Applied Acarology, 2018)

Update on the clinical application of deep brain stimulation in sleep dysfunction of Parkinson’s disease - Shuang Zou; Yu-Long Lan; Ya-Ping Hu; Xiao-Xue Yin; Wen-Long Liu; Tao Li; Zhanhua Liang (Acta Neurologica Belgica, 2018)

Nucleocapsid protein from porcine epidemic diarrhea virus isolates can antagonize interferon-λ production by blocking the nuclear factor-κB nuclear translocation - Ying Shan; Zi-qi Liu; Guo-wei Li; Cong Chen; Hao Luo; Ya-jie Liu; Xun-hui Zhuo; Xing-fen Shi; Wei-huan Fang; Xiao-liang Li (Journal of Zhejiang University-SCIENCE B, 2018)

Complementary feeding patterns among ethnic groups in rural western China - Peng-fei Qu; Ya Zhang; Jia-mei Li; Ruo Zhang; Jiao-mei Yang; Fang-liang Lei; Shan-shan Li; Dan-meng Liu; Shao-nong Dang; Hong Yan (Journal of Zhejiang University-SCIENCE B, 2018)

Administration of fentanyl via a slow intravenous fluid line compared with rapid bolus alleviates fentanyl-induced cough during general anesthesia induction - Min-qiang Liu; Feng-xian Li; Ya-kun Han; Jun-yong He; Hao-wen Shi; Li Liu; Ren-liang He (Journal of Zhejiang University-SCIENCE B, 2017)

Molecular identification of differential expression genes associated with sex pheromone biosynthesis in Spodoptera exigua - Ya-Nan Zhang; Long-Wa Zhang; Da-Song Chen; Liang Sun; Zhao-Qun Li; Zhan-Feng Ye; Mei-Yan Zheng; Jin-Bu Li; Xiu-Yun Zhu (Molecular Genetics and Genomics, 2017)

Erratum to: Transposon insertion resulted in the silencing of Wx-B1n in Chinese wheat landraces - Ling‑Ling Zhang; Hu Chen; Mi Luo; Xiao‑Wei Zhang; Mei Deng; Jian Ma; Peng‑Fei Qi; Ji‑Rui Wang; Guo‑Yue Chen; Ya‑Xi Liu; Zhi‑En Pu; Wei Li; et al. (Theoretical and Applied Genetics, 2017)

Transposon insertion resulted in the silencing of Wx-B1n in Chinese wheat landraces - Ling-Ling Zhang; Hu Chen; Mi Luo; Xiao-Wei Zhang; Mei Deng; Jian Ma; Peng-Fei Qi; Ji-Rui Wang; Guo-Yue Chen; Ya-Xi Liu; Zhi-En Pu; Wei Li; et al. (Theoretical and Applied Genetics, 2017)

A population association study of vitamin D receptor gene polymorphisms and haplotypes with the risk of systemic lupus erythematosus in a Chinese population - Xu-E Chen; Pu Chen; Shan-Shan Chen; Jin Lu; Ting Ma; Guang Shi; Ya Zhou; Ji Li; Liang Sheng (Immunologic Research, 2017)

Effect of rainfall on a colluvial landslide in a debris flow valley - Liang Qiao; Xing-min Meng; Guan Chen; Yi Zhang; Peng Guo; Run-qiang Zeng; Ya-jun Li (Journal of Mountain Science, 2017)

Establishment of mouse leukemia cell lines expressing human CD4/CCR5 using lentiviral vectors - Ya-jing Li; Fu-yan ZhuGe; Chang-chun Zeng; Jin-yang He; Ning Tan; Juan Liang (Virus Genes, 2017)

Identification of protein tyrosine phosphatase SHP-2 as a new target of perfluoroalkyl acids in HepG2 cells - Yu Yang; Qi-Yan Lv; Liang-Hong Guo; Bin Wan; Xiao-Min Ren; Ya-Li Shi; Ya-Qi Cai (Archives of Toxicology, 2017)

Enhanced Therapeutic Potential of Nano-Curcumin Against Subarachnoid Hemorrhage-Induced Blood–Brain Barrier Disruption Through Inhibition of Inflammatory Response and Oxidative Stress - Zong-yong Zhang; Ming Jiang; Jie Fang; Ming-feng Yang; Shuai Zhang; Yan-xin Yin; Da-wei Li; Lei-lei Mao; Xiao-yan Fu; Ya-jun Hou; Xiao-ting Fu; Cun-dong Fan; et al. (Molecular Neurobiology, 2017)

Hepatic expression of transcription factors affecting developmental regulation of UGT1A1 in the Han Chinese population - Ya-li Nie; Hang He; Jiang-feng Li; Xiang-guang Meng; Liang Yan; Pei Wang; Shu-jie Wang; Hong-zheng Bi; Li-rong Zhang; Quan-cheng Kan (European Journal of Clinical Pharmacology, 2017)

A R2R3-MYB transcription factor gene in common wheat (namely TaMYBsm1) involved in enhancement of drought tolerance in transgenic Arabidopsis - Meng-jun Li; Yu Qiao; Ya-qing Li; Zhan-liang Shi; Nan Zhang; Cai-li Bi; Jin-kao Guo (Journal of Plant Research, 2016)

Activation of mTOR signaling mediates the increased expression of AChE in high glucose condition: in vitro and in vivo evidences - Yao-Wu Liu; Liang Zhang; Yu Li; Ya-Qin Cheng; Xia Zhu; Fan Zhang; Xiao-Xing Yin (Molecular Neurobiology, 2016)

DSePA Antagonizes High Glucose-Induced Neurotoxicity: Evidences for DNA Damage-Mediated p53 Phosphorylation and MAPKs and AKT Pathways - Kun Wang; Xiao-yan Fu; Xiao-ting Fu; Ya-jun Hou; Jie Fang; Shuai Zhang; Ming-feng Yang; Da-wei Li; Lei-lei Mao; Jing-yi Sun; Hui Yuan; Xiao-yi Yang; et al. (Molecular Neurobiology, 2016)

Molecular Design, Structural Analysis and Antifungal Activity of Derivatives of Peptide CGA-N46 - Rui-Fang Li; Zhi-Fang Lu; Ya-Nan Sun; Shi-Hua Chen; Yan-Jie Yi; Hui-Ru Zhang; Shuo-Ye Yang; Guang-Hai Yu; Liang Huang; Chao-Nan Li (Interdisciplinary Sciences: Computational Life Sciences, 2016)

Characterization of the waxy gene in diploid Triticum L. and Aegilops L. species and its geographic distribution - Wei Li; Bang-Bo Fu; Zhe Li; Ya-Xi Liu; Zhi-En Pu; Peng-Fei Qi; Qian-Tao Jiang; Guo-Yue Chen; Ji-Rui Wang; Yu-Ming Wei; You-Liang Zheng (Genetic Resources and Crop Evolution, 2016)

Downregulation of Glutamate Transporter EAAT4 by Conditional Knockout of Rheb1 in Cerebellar Purkinje Cells - Nan-Wei Jiang; De-Juan Wang; Ya-Jun Xie; Liang Zhou; Li-Da Su; Huashun Li; Qin-Wen Wang; Ying Shen (The Cerebellum, 2016)

Structure and expression of phosphoglucan phosphatase genes of Like Sex Four1 and Like Sex Four2 in barley - Jian Ma; Shang Gao; Qian-Tao Jiang; Qiang Yang; Min Sun; Ji-Rui Wang; Peng-Fei Qi; Ya-Xi Liu; Wei Li; Zhi-En Pu; Xiu-Jin Lan; Yu-Ming Wei; et al. (Genetica, 2016)

On the variability of near-bed floc size due to complex interactions between turbulence, SSC, settling velocity, effective density and the fractal dimension of flocs - Yang Yang; Ya Ping Wang; Chunyan Li; Shu Gao; Benwei Shi; Liang Zhou; Dandan Wang; Gaocong Li; Chen Dai (Geo-Marine Letters, 2016)

Sediment resuspension in tidally dominated coastal environments: new insights into the threshold for initial movement - Yang Yang; Ya Ping Wang; Shu Gao; Xiao Hua Wang; Ben Wei Shi; Liang Zhou; Dan Dan Wang; Chen Dai; Gao Cong Li (Ocean Dynamics, 2016)

Salt tolerance and alterations in cytosine methylation in the interspecific hybrids of Fraxinus velutina and Fraxinus mandshurica - Fan-Suo Zeng; Lei-Lei Li; Nan-Song Liang; Xuan Wang; Xiang Li; Ya-Guang Zhan (Euphytica, 2015)

Reproductive management through integration of PGD and MPS-based noninvasive prenatal screening/diagnosis for a family with GJB2-associated hearing impairment - WenPing Xiong; DaYong Wang; Yuan Gao; Ya Gao; HongYang Wang; Jing Guan; Lan Lan; JunHao Yan; Liang Zong; Yuan Yuan; Wei Dong; SeXin Huang; et al. (Science China Life Sciences, 2015)

Characterization of genes encoding Starch Branching Enzyme I from Triticum monococcum and its diploid wheat relatives - Xiu-Ying Wang; Chang-Shui Wang; Jian Ma; Ji-Rui Wang; Ya-Xi Liu; Peng-Fei Qi; Wei Li; Zhi-En Pu; Xiu-Jin Lan; Yu-Ming Wei; You-Liang Zheng; Qian-Tao Jiang (Biologia, 2015)

ERK5 signalling pathway is essential for fluid shear stress-induced COX-2 gene expression in MC3T3-E1 osteoblast - Jin Jiang; Liang-gong Zhao; Yuan-jun Teng; Shao-long Chen; Li-ping An; Jing-ling Ma; Jing Wang; Ya-yi Xia (Molecular and Cellular Biochemistry, 2015)

Baseline sensitivity and control efficacy of fluazinam against Sclerotinia sclerotiorum - Hong-Jie Liang; Ya-Li Di; Jin-Li Li; Fu-Xing Zhu (European Journal of Plant Pathology, 2015)

Association between the CYP1A2 polymorphisms and risk of cancer: a meta-analysis - Wen-Xia Sun; Ying-Hua Chen; Zhi-Zhong Liu; Jian-Jun Xie; Wei Wang; Ya-Ping Du; Yu Chen; Xu-Liang Shen; Xiao-Feng He; Li-Xia Wu; Wu Wei; Lin Zhang (Molecular Genetics and Genomics, 2015)

LGI1 is Involved in the Development of Mouse Brain - Li-Da Su; Ya-Jun Xie; Liang Zhou; Ying Shen; Ying-Hong Hu (The Cerebellum, 2015)

Baseline sensitivity and control efficacy of DMI fungicide epoxiconazole against Sclerotinia sclerotiorum - Jin-Li Li; Xiang-Yang Liu; Ya-Li Di; Hong-Jie Liang; Fu-Xing Zhu (European Journal of Plant Pathology, 2015)

Lipopolysaccharides Upregulate Hepcidin in Neuron via Microglia and the IL-6/STAT3 Signaling Pathway - Zhong-Ming Qian; Xuan He; Tuo Liang; Ka-Chun Wu; Yik-Chun Yan; Li-Na Lu; Guang Yang; Qian Qian Luo; Wing-Ho Yung; Ya Ke (Molecular Neurobiology, 2014)

Microseismic monitoring of columnar jointed basalt fracture activity: a trial at the Baihetan Hydropower Station, China - Bing-Rui Chen; Qing-Peng Li; Xia-Ting Feng; Ya-Xun Xiao; Guang-Liang Feng; Lian-Xing Hu (Journal of Seismology, 2014)

Identification of a putative cognate sensor kinase for the two‐component response regulator HrpG , a key regulator controlling the expression of the hrp genes in X anthomonas campestris pv. campestris - Rui‐Fang Li; Guang‐Tao Lu; Lei Li; Hui‐Zhao Su; Guo‐fang Feng; Ya Chen; Yong‐Qiang He; Bo‐Le Jiang; Dong‐Jie Tang; Ji‐Liang Tang (Environmental Microbiology, 2014)
Summary The bacterial phytopathogen X anthomonas campestris pv. campestris ( Xcc ) relies on the hrp (hypersensitive response and pathogenicity) genes to cause disease and induce hypersensitive response ( HR ). The hrp genes of bacterial phytopathogens are divided into two groups. Xcc hrp genes belong to group II . It has long been known that the group II hrp genes are activated by an AraC ‐type transcriptional regulator whose expression is controlled by a two‐component system ( TCS ) response regulator (named HrpG in Xcc ). However, no cognate sensor kinase has yet been identified. Here, we present evidence showing that the Xcc open‐reading frame XC _3670 encodes a TCS sensor kinase (named HpaS ). Mutation of hpaS almost completely abolished the HR induction and virulence. Bacterial two‐hybrid and protein pull‐down assays revealed that HpaS physically interacted with HrpG . Phos‐tag™ SDS‐PAGE analysis showed that mutation in hpaS reduced markedly the phosphorylation of HrpG in vivo . These data suggest that HpaS and HrpG are most likely to form a TCS . We also showed that XC _3669 (named hpaR2 ), which is adjacent to hpaS and encodes a putative TCS response regulator, is required for full virulence but not HR induction. HpaR2 also physically interacted with HpaS , suggesting that HpaS may also form another TCS with HpaR2 .

Large-scale screening maize germplasm for low-phosphorus tolerance using multiple selection criteria - Li-tian Zhang; Jia Li; Ting-zhao Rong; Shi-bin Gao; Feng-kai Wu; Jie Xu; Meng-lu Li; Mo-ju Cao; Jing Wang; Er-liang Hu; Ya-xi Liu; Yan-li Lu (Euphytica, 2014)

A tripeptide (NSK) inhibits Japanese encephalitis virus infection in vitro and in vivo - Chen Li; Ling-ling Ge; Ya-ling Yu; Li Huang; Yue Wang; Ming-xia Sun; Hassan Ishag; Liang-xiao Ma; Xue-hua Li; Zhi-qiang Shen; Xiang Mao (Archives of Virology, 2014)

Anthropogenic effect on deposition dynamics of lake sediments based on 137Cs and 210Pbex techniques in Jiuzhaigou National Nature Reserve, China - Kangkang Liang; Xinxin Hu; Shiguang Li; Chengmin Huang; Ya Tang (Chinese Geographical Science, 2014)

Shapinggou: the largest Climax-type porphyry Mo deposit in China - Hong Zhang; Cong-Ying Li; Xiao-Yong Yang; Ya-Li Sun; Jiang-Hong Deng; Hua-Ying Liang; Rui-Long Wang; Bo-Hua Wang; Yu-Xian Wang; Wei-Dong Sun (International Geology Review, 2014)

Rice black-streaked dwarf virus genome segment S5 is a bicistronic mRNA in infected plants - Jian Yang; Heng-Mu Zhang; Lu Ying; Jing Li; Ming-Fang Lv; Li Xie; Pei-Pei Li; Xiao-Ya Liu; Dai Liang-Ying; Jian-Ping Chen (Archives of Virology, 2014)

Cell-penetrating fusion peptides OD1 and OD2 interact with Bcr–Abl and influence the growth and apoptosis of K562 cells - Hai-xia Wang; Heng Xiao; Liang Zhong; Kun Tao; Ya-juan Li; Shi-feng Huang; Jian-ping Wen; Wen-li Feng (Molecular and Cellular Biochemistry, 2014)

Synthesis and antibacterial evaluation of furan derivatives bearing a rhodanine moiety - Jian Che; Chang-Ji Zheng; Ming-Xia Song; Ya-Jing Bi; Yi Liu; Yin-Jing Li; Yan Wu; Liang-Peng Sun; Hu-Ri Piao (Medicinal Chemistry Research, 2014)

Charlson comorbidity index helps predict the risk of mortality for patients with type 2 diabetic nephropathy - You-Qun Huang; Rong Gou; Yong-Shu Diao; Qing-Hua Yin; Wen-Xing Fan; Ya-Ping Liang; Yi Chen; Min Wu; Li Zang; Ling Li; Jing Zang; Lu Cheng; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Remifentanil preconditioning alleviating brain damage of cerebral ischemia reperfusion rats by regulating the JNK signal pathway and TNF-α/TNFR1 signal pathway - Yan Zhang; Yan-Wei Li; Ya-Xin Wang; Hong-Tao Zhang; Xiao-Mei Zhang; Yu Liang; Xiu-Shan Zhang; Wen-Sheng Wang; Hai-Gen Liu; Yi Zhang; Ling Zhang; Yu-Hua Zheng (Molecular Biology Reports, 2013)

Major geochemical controls on fluoride enrichment in groundwater: A case study at Datong Basin, northern China - Liang Li; Yanxin Wang; Ya Wu; Junxia Li (Journal of Earth Science, 2013)

Influence of HbA1c on short-term blood pressure variability in type 2 diabetic patients with diabetic nephropathy - Fang Liu; Min Wu; Yan-huan Feng; Hui Zhong; Tian-lei Cui; You-qun Huang; Ya-ping Liang; Yong-shu Diao; Li Zang; Ling Li; Jing Zang; Hong-yu Qiu; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Up-regulation of Slc39A2(Zip2) mRNA in peripheral blood mononuclear cells from patients with pulmonary tuberculosis - Yan-ting Tao; Qing Huang; Ya-li Jiang; Xiao-lei Wang; Ping Sun; Yuanyuan Tian; Hai-liang Wu; Min Zhang; Si-bo Meng; Yu-shu Wang; Qing Sun; Lian-ying Zhang (Molecular Biology Reports, 2013)

Immune responses induced in HHD mice by multiepitope HIV vaccine based on cryptic epitope modification - Yinghui Li; Yuxiao Huang; Jiao Liang; Zhikai Xu; Yan Shen; Ning Zhang; Zhongxiang Liu; Ya Zhao (Molecular Biology Reports, 2013)

Meta-analysis of QTL associated with tolerance to abiotic stresses in barley - Wei-Tao Li; Chunji Liu; Ya-Xi Liu; Zhi-En Pu; Shou-Fen Dai; Ji-Rui Wang; Xiu-Jin Lan; You-Liang Zheng; Yu-Ming Wei (Euphytica, 2013)

Molecular diversity of restriction enzyme sites, Indels and upstream open reading frames (uORFs) of 5′ untransalted regions (UTRs) of Waxy genes in Triticum L. and Aegilops L. species - Wei Li; Zhen Gao; Wei Xiao; Yu-Ming Wei; Ya-Xi Liu; Guo-Yue Chen; Zhi-En Pu; Hua-Ping Chen; You-Liang Zheng (Genetic Resources and Crop Evolution, 2012)

Development of RT-LAMP and real-time RT-PCR assays for the rapid detection of the new duck Tembusu-like BYD virus - Tao Jiang; Juan Liu; Yong-Qiang Deng; Jing-Liang Su; Li-Juan Xu; Zhi-Hui Liu; Xiao-Feng Li; Xue-Dong Yu; Shun-Ya Zhu; George Fu Gao; E-De Qin; Cheng-Feng Qin (Archives of Virology, 2012)

Comparative analysis of essential oil components of Evodia rutaecarpa (Juss.) Benth. var. officinalis (Dode) Huang and Evodia rutaecarpa (Juss.) Benth. - Guang-Xian Cai; Dan Huang; Shun-Xiang Li; Fei Xu; Lu Wang; Yan-Hui Lu; Liang Cao; Bao-Yang Wei; Ya Li; Ping Cai (Natural Product Research, 2012)

A new benzodioxocinone from the leaves of Cinnamomum tenuifolium - Hsin-Liang Chen; Soong-Yu Kuo; Yun-Ping Li; Ya-Fei Kang; Yu-Ting Yeh; Jin-Cherng Huang; Chung-Yi Chen (Natural Product Research, 2012)

Association of STAT4 rs7574865 polymorphism with autoimmune diseases: a meta-analysis - Ya-ling Liang; Hua Wu; Xi Shen; Pei-qiang Li; Xiao-qing Yang; Li Liang; Wei-hua Tian; Li-feng Zhang; Xiao-dong Xie (Molecular Biology Reports, 2012)

Purification and characterization of trypsin from the pyloric ceca of orange-spotted grouper, Epinephelus coioides - Chun-Hung Liu; Ya-Li Shiu; Jue-Liang Hsu (Fish Physiology and Biochemistry, 2012)

Urotensin upregulates transforming growth factor-β1 expression of asthma airway through ERK-dependent pathway - Wei-xi Zhang; Ya-feng Liang; Xiao-ming Wang; Ying Nie; Lei Chong; Li Lin; Chun Chen; Chang-chong Li (Molecular and Cellular Biochemistry, 2012)

Cloning and ontogenetic expression of the uncoupling protein 1 gene UCP1 in sheep - Ya-Nan Yuan; Wen-Zhong Liu; Jian-Hua Liu; Li-Ying Qiao; Jian-Liang Wu (Journal of Applied Genetics, 2012)

Mapping stripe rust resistance gene YrSph derived from Tritium sphaerococcum Perc. with SSR, SRAP, and TRAP markers - Shi-Sheng Chen; Guo-Yue Chen; Hua Chen; Yu-Ming Wei; Wei Li; Ya-Xi Liu; Deng-Cai Liu; Xiu-Jin Lan; You-Liang Zheng (Euphytica, 2012)

Characterization of acute renal allograft rejection by proteomic analysis of renal tissue in rat - Gang Chen; Jing-bin Huang; Jie Mi; Yun-feng He; Xiao-hou Wu; Chun-li Luo; Si-min Liang; Jia-bing Li; Ya-xiong Tang; Jie Li (Molecular Biology Reports, 2012)

Analysis of Lanthanide-Induced Conformational Change of the C-Terminal Domain on Centrin - Ya-Qin Zhao; Jun Yan; Li Song; Ya-Nan Feng; Ai-Hua Liang; Bin-Sheng Yang (Journal of Fluorescence, 2012)

Effect of microcystin-LR on protein phosphatase 2A and its function in human amniotic epithelial cells - Jing Liang; Tan Li; Ya-li Zhang; Zong-lou Guo; Li-hong Xu (Journal of Zhejiang University-SCIENCE B, 2011)

Increased production of succinic acid in Escherichia coli by overexpression of malate dehydrogenase - Li-ya Liang; Rong-ming Liu; Jiang-feng Ma; Ke-quan Chen; Min Jiang; Ping Wei (Biotechnology Letters, 2011)

Genetic polymorphism analysis of 15 STR loci in Chinese Hui ethnic group residing in Qinghai province of China - Ya-jun Deng; Bo-feng Zhu; Chun-mei Shen; Hong-dan Wang; Jing-feng Huang; Yuan-zhe Li; Hai-xia Qin; Hao-fang Mu; Jie Su; Jie Wu; Bo Zhang; Shuan-liang Fan (Molecular Biology Reports, 2011)

Determination of optimal carbon source and pH value for sclerotial formation of Polyporus umbellatus under artificial conditions - Yong-Mei Xing; Juan Chen; Ya-Li Lv; Han-Qiao Liang; Shun-Xing Guo (Mycological Progress, 2011)

Genetic analysis of starch paste viscosity parameters in glutinous rice (Oryza sativa L.) - Chang-Jie Yan; Zhi-Xi Tian; Yu-Wei Fang; Ya-Chun Yang; Jian Li; Sheng-Yuan Zeng; Shi-Liang Gu; Chen-Wu Xu; Shu-Zhu Tang; Ming-Hong Gu (Theoretical and Applied Genetics, 2011)

Platelet adhesion and fusion to endothelial cell facilitate the metastasis of tumor cell in hypoxia-reoxygenation condition - Na Zhang; Wen-Jian Zhang; Han-Qing Cai; Hong-Lin Liu; Liang Peng; Cheng-Hui Li; Li-Ya Ye; Shi-Qing Xu; Zhi-Hua Yang; Jin-Ning Lou (Clinical & Experimental Metastasis, 2011)

Frequent occurrence of unreduced gametes in Triticum turgidum–Aegilops tauschii hybrids - Lian-Quan Zhang; Deng-Cai Liu; You-Liang Zheng; Ze-Hong Yan; Shou-Fen Dai; Yun-Fang Li; Qi Jiang; Ya-Qing Ye; Yang Yen (Euphytica, 2010)

Distributions of HLA-A and -B alleles and haplotypes in the Yi ethnic minority of Yunnan, China: relationship to other populations - Bo-feng Zhu; Guang Yang; Chun-mei Shen; Hai-xia Qin; Shun-zhi Liu; Ya-jun Deng; Shuan-liang Fan; Li-bin Deng; Feng Chen; Ping Zhang; Jie Fang; Li-ping Chen; et al. (Journal of Zhejiang University-SCIENCE B, 2010)

Enhancement of mucosal immune response against the M2eHBc+ antigen in mice with the fusion expression products of LTB and M2eHBc+ through mucosal immunization route - Guo-guang Zhang; Dong-xiao Li; Hui-huang Zhang; Ya-ming Zeng; Liang Chen (Veterinary Research Communications, 2009)

Molecular Identification of cDNA, Immunolocalization, and Expression of a Putative Odorant-Binding Protein from an Asian Honey Bee, Apis cerana cerana - Hong-Liang Li; Ya-Li Zhang; Qi-Kang Gao; Jia-An Cheng; Bing-Gan Lou (Journal of Chemical Ecology, 2008)

Evidence of Gene Conversion in the Evolutionary Process of the Codon 41/42 (-CTTT) Mutation Causing β-Thalassemia in Southern China - Wen Zhang; Wang-Wei Cai; Wei-Ping Zhou; Hai-Peng Li; Liang Li; Wei Yan; Qin-Kai Deng; Ya-Ping Zhang; Yun-Xin Fu; Xiang-Min Xu (Journal of Molecular Evolution, 2008)

Expression of a truncated ripening inhibitor (RIN) protein from tomato and production of an anti-RIN antibody - Hong-Liang Zhu; Ben-Zhong Zhu; Ya-Li Zhang; Yi Shao; Xiao-Guang Wang; Yuan-Hong Xie; An-Jun Chen; Ying-Cong Li; Hui-Qin Tian; Yun-Bo Luo (Biotechnology Letters, 2007)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)

Selection of biochemical mutants of Aspergillus niger with enhanced extracellular ribonuclease production - Ya-Hong Xiong; Jian-Zhong Liu; Hai-Yan Song; Li-Ping Weng; Liang-Nian Ji (World Journal of Microbiology and Biotechnology, 2004)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)